Transforming Dental Care: Integrating Geriatric Dentistry, Gerodontology, and Digital Marketing in Public Health - Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida; Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida (Digital Marketing for Public Dental Health: Global Impact Strategies, 2027)
The aging of the global population presents a significant challenge to public health, demanding innovative and sustainable dental approaches. This integrative literature review synthesizes research on the intersection of Geriatric Dentistry, Gerodontology, and digital marketing and communication str...

Determinants of Healthcare Professionals’ Intentions to Use Telemedicine for Elderly Care in Algeria: A Technology Acceptance Model Approach - Mouloudj, Kamel; Njoku, Anuli; Bouarar, Ahmed Chemseddine; Martínez Asanza, Dachel; Evans, Marian A.; Baviskar, Snehal (Geriatrics, 2026)
Background/Objectives: Telemedicine offers significant potential to improve the quality and accessibility of geriatric care, particularly in resource-constrained settings. However, its effective implementation depends largely on healthcare professionals’ acceptance and willingness to use such systems. Drawing on an extended Technology Acceptance Model (TAM), this study examines the determinants of doctors’ and nurses’ intentions to adopt telemedicine for elderly care in Algeria, with particular emphasis on self-efficacy and institutional support. Methods: This cross-sectional study employed a structured questionnaire administered to 130 healthcare professionals, including physicians and nurses, in Algeria. Hierarchical multiple regression analysis was conducted to test the proposed hypotheses and assess the incremental explanatory power of the extended model. Results: The extended TAM accounted for 48.7% of the variance in intention to use telemedicine. Institutional support (β = 0.432, p < 0.001) and self-efficacy (β = 0.264, p = 0.001) emerged as the strongest predictors. Perceived ease of use (β = 0.178, p = 0.038) and perceived usefulness (β = 0.139, p = 0.021) also had significant positive effects. The inclusion of self-efficacy and institutional support increased the model’s explanatory power by 23.5%. Conclusions: The findings highlight the critical role of organizational support mechanisms, digital competencies, and system usability in fostering telemedicine adoption among healthcare professionals. The study provides practical implications for policymakers and healthcare institutions, emphasizing the need for targeted training programs, supportive infrastructure, and institutional policies that enhance confidence and facilitate the integration of telemedicine into clinical workflows.
Keywords: Algeria; Technology Acceptance Model (TAM); cross-sectional study; dept.pch; digital health; elderly care; healthcare professionals; institutional support; self-efficacy; telemedicine

Racial Disparities and the Use of Artificial Intelligence for Predicting Maternal Mortality: A Literature Review - Gonçalves dos Santos, Gustavo; Njoku, Anuli; Mass, Ana Carolina Pereira; Ribeiro, Ellen Eduarda Santos; Oliveira, Letícia Eduarda de; Lima, Maria Julia Cunha Silva; Ferro, Taís de Abreu; Pirozi, Lilian Reinaldi Ribeiro; Peregrino, Antônio Augusto de Freitas; Santos, Célia Maria Pinheiro dos; Viana, Lucia Helena Ferreira; Sousa, Marilda Gonçalves de; et al. (Epidemiologia, 2026)
Background: Maternal mortality remains a major global health challenge, disproportionately affecting black and Indigenous women. Hypertensive disorders of pregnancy and postpartum hemorrhage are the leading direct causes of maternal death. Artificial intelligence (AI) tools have emerged as potential strategies for predicting these complications, yet concerns persist about their equity and validation across racial groups. Methods: A rapid review was conducted in five databases, PubMed, EMBASE, Web of Science, Scopus and LILACS, to synthesize recent evidence on the use of AI for preventing maternal mortality due to hypertension and postpartum hemorrhage. Studies published in the last five years that included racial or ethnic data were selected and analyzed narratively. Results: Ten studies met the inclusion criteria, showing high predictive accuracy of AI models (AUROC often >0.95) for severe maternal outcomes. However, few models incorporated racial variables or underwent external validation in racially diverse or low-resource populations. Evidence suggests that unrepresentative datasets may perpetuate or exacerbate existing health inequities. Conclusions: AI demonstrates strong technical performance in predicting maternal complications but limited equity in application. Broader racial representation, external validation, and ethical governance are essential for ensuring that AI-based tools reduce rather than reinforce racial disparities in maternal mortality.
Keywords: artificial intelligence; dept.pch; hypertension; maternal mortality; postpartum hemorrhage; racial disparities in health

Climate Justice: Access to Safe Drinking Water and Health—A Legal Discourse - Njoku, Anuli U.; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Addressing the issues of water insecurity and unequal access to water has been a priority of the Sustainable Development Goals. Poor sanitation and inadequate access to drinking water are the second leading causes of death among children worldwide. Access to safe drinking water is a fundamental human right. Climate change represents one of public health’s greatest challenges and significantly exacerbates health disparities. According to the World Health Organization, approximately 3.6 billion people reside in areas highly vulnerable to the effects of climate change. Furthermore, climate change is anticipated to result in roughly 250,000 additional deaths each year between 2030 and 2050. In the United States, climate impacts such as severe storms and floods, escalating wildfires, extreme heat, poor air quality, and diminishing access to food and water disproportionately endanger Black, Brown, and Indigenous communities, low-income groups, people with disabilities, women, children, older adults, and others, making them more susceptible to the harmful health effects of climate change. The formulation and implementation of climate policies are essential to address the negative impacts of climate change. This chapter aims to: (a) describe the effects of climate change on access to safe drinking water; (b) emphasize the implications of climate change on drinking water disparities; (c) highlight policies to mitigate the effects of climate change; and d) discuss recommendations to tackle climate change and inequities in access to water. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Climate change; Environmental injustice; Health disparities; Water disparity; Water injustice; Water insecurities; Water scarcity; dept.pch

Highlighting the power of Photovoice exhibits as a tool for resistance, equity, and social change - McMorrow, Shannon; Breny, Jean (Health Promotion Practice, 2026)
Keywords: Citizen journalism; Community-based participatory research; Health equity; Health promotion; Perspective (graphical); Photovoice; Power (physics); Public health; community engagement; dept.pch; participatory research; photovoice; photovoice exhibits; public scholarship; racial equity; refugees; scholar activism; social change research

Consumption patterns of drinking water and its impact on public health - Njoku, Anuli; Agbalenyo, Martin (Climate Change, Drinking Water Security, and Public Health: Global Challenges and Solutions, 2026)
Keywords: Consumption (sociology); Globe; Health equity; Investment (military); Population; Population health; Public health; Social determinants of health; Water supply; dept.pch

Social Marketing for Health Equity: Promoting Preventive Health Behavior Among Women in Rural Communities - Mouloudj, Kamel; Alameri, Sarah Ali Saeed; Evans, Marian A.; Almado, Alaa Abdulkareem Ghaleb; Mahmoud, Basheer Ismail; Asanza, Dachel Martínez (International Journal of Environmental Research and Public Health, 2026)
Preventive health behaviors play a critical role in reducing disease risks and improving public health outcomes, particularly among vulnerable populations such as women in rural communities. However, limited research has explored the determinants of intentions to adopt preventive health behaviors in developing contexts among women in rural communities. This study applies and extends the Theory of Planned Behavior (TPB) to examine these determinants in Algeria. A cross-sectional study was conducted using convenience sampling among 205 women in rural communities aged 20–60 years across five Algerian cities. Data were collected through a self-administered questionnaire and analyzed using hierarchical multiple regression. The results indicate that attitude, subjective norms, and perceived behavioral control have significant positive effects on behavioral intention. The inclusion of health literacy significantly enhances the model’s explanatory power, with higher literacy associated with stronger intentions. In contrast, perceived healthcare discrimination does not have a statistically significant effect. The extended model explains 57.5% of the variance in behavioral intention. These findings underscore the importance of psychosocial and informational factors in shaping preventive health intentions and support the extension of TPB in this context. They also provide practical implications for policymakers and healthcare practitioners to design targeted social marketing interventions aimed at improving preventive health behaviors and reducing health disparities among women in rural communities. © 2026 by the authors.
Keywords: Behavior change; Health belief model; Health care; Health literacy; Health promotion; Psychological intervention; Psychosocial; Public health; Social marketing; Theory of planned behavior; dept.pch; health equity; health literacy; health policy; perceived healthcare discrimination; preventive health behaviors; women in rural communities

A Scoping Review of Skin Whitening Products: Users’ Knowledge and Motivations, Marketing Strategies, and Adverse Health Effects - Njoku, Anuli; Sawadogo, Wendemi; Pierce, Taryn; Albert, Kaleigh; Plummer, Fabian (International Platform of Registered Systematic Review and Meta-analysis Protocols, 2025)
Keywords: Adverse effect; Business; Marketing; Medicine; Pharmacology; dept.pch

Moving beyond “risky behavior”: a qualitative interview study exploring geosocial networking app use by sexual minority men and women in the UK and USA - Madden, Hannah; Timpson, Hannah; Breny, Jean; Hope, Vivian; Porcellato, Lorna (International Journal of Sexual Health, 2025)
Objective: Research on use of geosocial networking (GSN) applications (e.g. Grindr, Tinder) by sexual minorities has primarily focused on risky behavior and negative health outcomes (e.g. sexually transmitted infections/HIV, drugs, alcohol, violence) among men who have sex with men. Taking a sex-positive approach, this study aimed to understand how sexual minority GSN app users in the UK and USA perceive impacts on their health and how they manage potential risks. Differences between countries and genders are explored. Design and methods: Qualitative, cross-cultural study in Merseyside (UK) and Connecticut (USA). Photo-elicitation (fake dating profiles) was used in semi-structured interviews conducted with app users seeking same gender partners (n = 31; 15 women, and 16 men) in 2018-2019. Participants were recruited through local LGBTQ+ organizations, social media and from a previous survey, within a quota sampling framework. Transcripts were analyzed using reflexive thematic analysis. Results: Perceived positive health impacts included social and romantic/sexual connections, boosts to self-esteem, and pleasurable sexual experiences. Some negative outcomes were reported, mainly by men, including rejection and low self-esteem, and racism and discrimination. Participants of all genders used strategies to reduce risks to health. Women were particularly cautious of men on apps. No differences between UK and the USA were noted. Conclusions: GSN apps can enable positive sexual experiences and have the potential to increase social cohesion and improve mental wellbeing for stigmatized sexual minorities. All participants took measures to protect both their physical safety and mental wellbeing. Using a sex-positive health promotion approach could empower app users to build on their personal strengths and resources. Although GSN app companies may need to do more to tackle discrimination, apps show a promising opportunity for reducing isolation and health inequities. The similarity of the findings in both areas suggests evidence from the USA may be applicable in the UK.
Keywords: Clinical psychology; Gerontology; Medicine; Psychology; Qualitative research; Sexual behavior; Sexual minority; Sexual orientation; Social psychology; Social science; Sociology; dept.pch

Health behavior and health promotion theories: application in environmental sciences and health - Njoku, Anuli; Molla, Azizur; Tohura, Sharaban (Handbook of Concepts in Health, Health Behavior and Environmental Health, 2025)
Keywords: Environmental health; Health behavior; Health promotion; Medicine; Nursing; Psychology; Public health; dept.pch

From heroes to zeroes: the unraveling support for public health in COVID pandemic-era connecticut - Ketner, Amanda; Micca, Olivia; Barnes, Aaliyah; Ent, Emily; Segala, Shelby; Breny, Jean; DeMaro, Gabriella (Journal of Public Health Management and Practice, 2025)
Keywords: Burnout; Business; Clinical psychology; Coronavirus disease 2019 (COVID-19); Emotional exhaustion; Feeling; Focus group; Health care; Marketing; Medicine; Mental health; Nursing; Pandemic; Personal protective equipment; Political science; Psychiatry; Psychology; Public health; Public relations; Qualitative research; Social psychology; Sociology; Staffing; Thematic analysis; dept.pch

Investigating antecedents of intention to use green agri-food delivery apps: merging TPB with trust and electronic word of mouth - Mouloudj, Kamel; Aprile, Maria; Bouarar, Ahmed; Njoku, Anuli; Evans, Marian; Oanh, Le; Asanza, Dachel; Mouloudj, Smail (Sustainability, 2025)
The rapid expansion of digital platforms has significantly influenced consumer purchasing behaviors, particularly in the agri-food sector. Therefore, this paper investigates the key factors driving customers’ intention to use green agri-food delivery apps (GAFDAs) by integrating trust and electronic word of mouth (eWOM) into the Theory of Planned Behavior (TPB) framework. Additionally, this study examines gender as a moderating variable, assessing whether its influence alters the relationships between key determinants and behavioral intention. Data were collected from 252 Algerian consumers, and the proposed model was tested using SmartPLS 4 and SPSS 26.0. The results confirm that attitude, subjective norms, perceived behavioral control (PBC), trust, and eWOM positively and significantly influence the intention to use GAFDAs, with PBC emerging as the strongest predictor. Moreover, gender moderates the effect of trust on behavioral intention, with trust significantly influencing men’s adoption decisions but not those of females. In contrast, subjective norms and PBC are stronger predictors for female consumers. These findings highlight the importance of gender-specific marketing strategies to enhance GAFDA adoption. This study contributes to the literature by extending TPB with trust, eWOM, and gender moderation, offering valuable insights for marketers, policymakers, and app developers promoting sustainable food consumption.
Keywords: Advertising; Artificial intelligence; Business; Computer science; Control (management); Food delivery; Marketing; Psychology; Theory of planned behavior; Word of mouth; dept.pch

Maternal Mortality Among Black Women in Brazil: A Retrospective Cohort Study - dos Santos, Gustavo; Njoku, Anuli; Mafetoni, Reginaldo; de Oliveira Sanfelice, Clara; Nicolau, Ana; Parenti, Patrícia; de Oliveira, Cely; López-Pedraza, Leticia; Mouta, Ricardo; Zihlmann, Karina; Lima, Cindy; Júnior, Cícero; et al. (International Journal of Environmental Research and Public Health, 2026)
BACKGROUND: Maternal mortality in Brazil remains a critical indicator of social and racial inequalities, reflecting structural failures in access to and quality of obstetric care. Black women, particularly those categorized as black or brown, are at a higher risk of dying during pregnancy, childbirth, or the postpartum period. This is the result of the intersection of institutional racism, poverty, and social vulnerabilities. This study aimed to analyze trends and associated factors of maternal mortality among black women in Brazil from 2000 to 2020. METHODS: This is a retrospective cohort analytical study using data from the Brazilian Mortality Information System. The sample included women aged 10 to 49 years whose underlying cause of death was classified under ICD-10 codes O00-O99. Descriptive and bivariate analyses were conducted, as well as Poisson and multinomial logistic regressions to estimate adjusted risk ratios according to skin color, education, region, type, and place of death. RESULTS: A total of 40,907 maternal deaths were identified, with 59.2% occurring among black women. The maternal mortality ratio was 39% higher among black women compared to white women and more than double among Indigenous women. Low education, residence in the North and Northeast regions, deaths outside hospital settings, and lack of formal investigation were independently associated with increased risk. Direct obstetric causes accounted for most deaths, with hypertensive disorders and puerperal complications being the leading conditions. CONCLUSIONS: Maternal mortality among black women in Brazil reveals deep structural inequalities. Urgent public policies that incorporate an intersectional perspective, addressing race, gender, and class, are necessary to reduce disparities and ensure equitable and dignified maternal healthcare.
Keywords: Black women; Cohort study; Inequality; Maternal health; Maternal morbidity; Public health; Retrospective cohort study; dept.pch

Sleep Duration, Disturbances, and Health-Related Quality of Life in Stroke Survivors - Sawadogo, Wendemi; Adera, Tilahun; Burch, James; Alattar, Maha; Perera, Robert; Howard, Virginia (Archives of Physical Medicine and Rehabilitation, 2025)
Keywords: Insomnia; Odds; Odds ratio; Quality of life; Quality of life (healthcare); Rehabilitation; Sleep (system call); Sleep disturbances; Sleep duration; Stroke (engine); Stroke survivors; dept.pch

Exposure to Endocrine-Disrupting Chemicals and Early Onset of Menarche: A Systematic Review - Njoku, Anuli; Al-Hassan, Mousa; Tohura, Sharaban; Albert, Kaleigh; Pierce, Taryn; Sawadogo, Wendemi (Pollutants, 2025)
There has been a decline in the age at which girls experience menarche worldwide. Research suggests that exposure to endocrine-disrupting chemicals is linked to negative health consequences, including early onset of menarche. This systematic review examined the association between exposure to endocrine-disrupting chemicals (EDCs) and the early onset of menarche. Comprehensive searches of the PubMed, Embase, Web of Science, and Scopus databases were conducted to find relevant studies published from inception to November 2024. Exposure to certain EDCs, such as particulate matter and phthalates, showed significant associations with earlier menarche onset, while exposure to other EDCs (e.g., pyrethroids) was linked to delayed menarche timing. Overall, there were mixed findings in the relationships between various EDC exposures and menarche onset. Few studies investigated how exposure to EDCs and early menarche differed by race and ethnicity. This underscores the need for more studies that examine the relationship between early menarche onset and exposure to endocrine-disrupting substances. Education and policy approaches are also warranted to address this issue.
Keywords: Age of onset; Epidemiology; MEDLINE; Menarche; Risk assessment; Scopus; dept.pch; endocrine-disrupting chemicals; environmental health; menarche; puberty; reproductive health

The Relationship Between Sleep Disorders and Stroke - Sawadogo, Wendemi; Adera, Tilahun (Handbook of the Behavior and Psychology of Disease, 2025)
Stroke is a leading cause of death and disability worldwide. It is a serious disease caused by a disruption of blood flow in the brain resulting from either blockage of blood flow to the brain (ischemic stroke) or sudden bleeding in the brain (hemorrhagic stroke). Stroke survivors experience more sleep disorders than the general population. Sleep disorders could also increase the risk of stroke even in individuals who have no history of stroke. Obstructive sleep apnea and insomnia are the most common sleep disorders associated with increased risk of stroke. Long sleep duration (≥9 h/day) and circadian rhythm changes have also been linked to an increased risk of stroke. This chapter summarizes the current evidence on the relationship between sleep disorders and stroke. © 2025 Springer Nature Switzerland AG.
Keywords: Central sleep apnea; Circadian rhythm disruption; Hypersomnia; Insomnia; Obstructive sleep apnea; Parasomnia; Sleep disorders; Sleep disturbances; Sleep movement disorders; Stroke; dept.pch

Association Between Social Determinants of Health and Borderline Personality Disorder: A Systematic Review - Guerrera, Patrick; Sawadogo, Wendemi; Baviskar, Snehal; Pham, Julie; Patel, Nirali; Cyrus, John (Personality and Mental Health, 2025)
Keywords: Association (psychology); Borderline personality disorder; Context (archaeology); Interpersonal relationship; Mental health; Personality; PsycINFO; Social determinants of health; borderline personality disorder; dept.pch; education; income; social determinants of health; social support; socioeconomic status

WIC Participation During Pregnancy and Low and Very Low Birth Weight by Race and Ethnicity - Sawadogo, Wendemi; McGuire, Neil; Evans, Marian; Tangbe, Praise (Journal of Nutrition Education and Behavior, 2025)
Keywords: Anthropology; Biology; Ethnic group; Gender studies; Low birth weight; Medicine; Obstetrics; Pregnancy; Race (biology); Sociology; WIC; dept.pch; low birth weight; peer-reviewed; pregnancy; race and ethnicity; very low birth weight

Health Information Access Behaviors by Sexual Orientation: A Secondary Data Analysis of the National Health Interview Survey - Gagnon, Kelly; Corey, Stephanie; Gordon, Jacob; Risisky, Deb; Coulter, Robert (Journal of Homosexuality, 2025)
Sexual minority (SM) adults are at increased risk for adverse health outcomes and face unique barriers to engagement and retention in healthcare, including stigma and discrimination. Given known barriers to care, SM adults may prefer online platforms due to limited access to in-person clinical care and fear of discrimination. To date, there is limited knowledge of these behaviors among subgroups of SM adults. This study was a cross-sectional, secondary data analysis of the United States National Health Interview Survey (NHIS) Adult Sample Data Set, 2018. Utilizing descriptive statistics and multivariable logistic regressions, we found that bisexual females had significantly greater odds (AOR = 1.58, CI: 1.04-2.39) of seeking health information online compared to straight females. Similarly, when compared to their straight male counterparts, gay males had significantly higher odds of seeking health information online in the past 12 months (AOR = 2.96, 95% CI: 2.00-4.37). These findings indicate the need for targeting messaging and interventions to address the health concerns of these populations. It also suggests that virtual platforms are viable and perhaps preferred for these subgroups of SM adults. Through continued efforts and research, the field can target relevant health information to populations who need it most by leveraging where they seek it.
Keywords: Environmental health; Health Information National Trends Survey; Health care; Health information; Homosexuality; Medicine; National Health Interview Survey; Orientation (vector space); Political science; Psychology; Reproductive health; Sexual behavior; Sexual minority; Sexual minority health; Sexual orientation; Social psychology; Survey data collection; bisexual women; dept.pch; gay men; health information access; healthcare utilization; online health information; peer-reviewed; public health

Mothers who use opioids and are involved in the criminal justice system: A transformative justice approach - Boeri, Miriam; Lamonica, Aukje; Smith, Sierra (Human Organization, 2025)
Keywords: Criminal justice; Criminology; Developmental psychology; Economic Justice; Law; Political science; Psychology; Restorative justice; Sociology; Theory of criminal justice; Transformative learning; dept.pch; mothers; opioids; recovery; relapse

Insomnia Symptoms, Mental Health Diagnosis, Mental Health Care Utilization, and Perceived Barriers in U.S. Males and Females - Sawadogo, Wendemi; Njoku, Anuli; Jegede, Joy (Journal of Clinical Medicine, 2025)
Objective: We aim to determine the association between insomnia symptoms and mental health in females and males and compare mental health care utilization and perceived barriers between females and males with insomnia symptoms. Methods: This is a cross-sectional study using the National Health Interview Survey. Insomnia symptoms included self-reported “trouble falling asleep”, ‘trouble staying asleep”, and “waking up feeling not well rested”. Mental health included self-reported anxiety and depression. Multivariable logistic regression was used to assess the association between insomnia symptoms and mental health in females and males. Results: A total of 26,691 adults were included. The mean age was 48.2 years; 51.4% were females, and 48.6% were males. Insomnia symptoms were associated with anxiety and depression for both females and males. These associations were stronger in younger adults (<50 years) than older adults (≥50 years). Females with insomnia symptoms were more likely to receive mental health care (OR = 1.7; 95% CI = 1.53, 1.87) but also to delay mental health care because of its cost (OR = 1.96; 95% CI: 1.67, 2.30) or needed mental health care but did not get it because of the cost (OR = 2.14; 95% CI: 1.82, 2.50) than their males counterpart. Conclusions: Insomnia symptoms were associated with mental health in females and males, being stronger in younger adults than older adults, with gender differences in mental health care utilization and financial barriers to mental health care. Holistic approaches involving prevention and better access to mental health care are warranted.
Keywords: Anxiety; Cross-sectional study; Depression (economics); Feeling; Health care; Insomnia; Internal medicine; Logistic regression; Medicine; Mental health; Psychiatry; Psychology; dept.pch; dept.swk; peer-reviewed

Impact of an emergency department take-home naloxone program on subsequent overdose and death - Wills, Brandon; Keyser‐Marcus, Lori; Sawadogo, Wendemi; Gizaw, Andinet; Melmer, Monica; Nguyen, Tammy; Nguyen, Natalie; Davis, Theresa; Ringwood, Katy; Moeller, F. (Heliyon, 2025)
Abstract Background Patients presenting to the emergency department (ED) following nonfatal opioid overdose represent a high-risk population with 5 % of patients dying within a year of the index visit. Objective To evaluate subsequent overdose and death before and after the implementation of an ED discharge naloxone program. Methods This was a retrospective cohort study of ED patients who presented at the Virginia Commonwealth University Health ED with an Opioid Use Disorder (OUD) chief complaint before and after a discharge naloxone program. The pre-naloxone cohort was consecutive ED OUD patients from August 15, 2021, to August 14, 2022, and the post-naloxone cohort from August 15, 2022, to August 14, 2023. The outcomes were subsequent overdose, ED visit to same hospital (VCU), and death within six months of the index visit. Results In total, 1,053 patients were included, of which 529 were in the pre-naloxone cohort and 524 patients in the post-naloxone cohort. The mean age was 44.2 years (SD = 14.0) and 69 % were males. There was a reduction in overdose requiring ED visiting (subsequent ED overdose) and death (4.6 % vs 9.2 % p = 0.03 and 2.0 % vs 5.6 % p = 0.02 respectively) in the post-naloxone cohort compared to the pre-naloxone cohort. After adjusting for sociodemographic and clinical factors, there was a 48 % reduction in the risk of subsequent ED overdose (RR = 0.52, 95 % CI: 0.27, 1.02) and a 63 % reduction in the risk of death (RR = 0.37, 95 % CI: 0.14, 0.95). Conclusion Implementing an ED take-home naloxone program was associated with a reduction in subsequent overdose and death at six months.
Keywords: (+)-Naloxone; Drug overdose; Emergency department; Emergency medicine; Internal medicine; Medical emergency; Medicine; Naloxone; Opioid; Opioid antagonist; Opioid overdose; Poison control; Psychiatry; dept.pch; peer-reviewed

Neighborhood Socioeconomic Status and Breastfeeding Initiation and Duration Among Primiparous Black Women - Griswold, Michele; Crawford, Sybil; Person, Sharina; Rosenberg, Lynn; Palmer, Julie; Cozier, Yvette (Breastfeeding Medicine, 2025)
Background: Social determinants of health account for racial inequities in breastfeeding rates in the United States. There is a gap in the role of neighborhood socioeconomic status (NSES) as it relates to breastfeeding disparities. Methods: Using longitudinal data from the Black Women’s Health Study, we assessed associations of NSES with breastfeeding initiation and duration in a cohort of primiparous U.S. Black women. We also explored associations within strata of important economic indicators, including education, occupation, and marital status. Results: Breastfeeding initiation ( n = 2,705) increased with NSES quartile, from 75.2% in the lowest quartile to 88.3% in the highest quartile ( p < 0.0001). Compared with women living in the highest NSES quartile, those in the lowest quartile had a 41% (odds ratio: 0.59 [95% confidence interval: 0.43, 0.81]) decreased odds of initiating breastfeeding. For breastfeeding duration ( n = 2,172), women residing in NSES quartiles 1–3 were significantly less likely ( p < 0.0001) to breastfeed (44.4%) for 6+ months compared with those living in the highest quartile (62.8%). Adjusted relative risks for those in quartiles 1–3 compared with 4 (highest) were 0.63 (0.45, 0.87), 0.50 (0.37, 0.68), and 0.64 (0.47, 0.86), respectively ( p = 0.0001). There was no statistically significant evidence of effect modification by education, occupation, marital status, and region ( P interaction = >0.05). Conclusion: Living in a lower NSES environment was associated with reduced breastfeeding initiation and duration compared with a higher NSES environment. Research is needed to understand the mechanisms by which neighborhood-level factors influence breastfeeding initiation and duration for Black women in the United States.
Keywords: Black women; Breast feeding; Breastfeeding; Demography; Duration (music); Environmental health; Medicine; Obstetrics; Pediatrics; Population; Socioeconomic status; dept.pch; peer-reviewed

Recent Intimate Partner Violence, Sexual Risk and HIV-Related Worry: Examining the Mediating Effects of Sexual Autonomy - Willie, Tiara; Callands, Tamora; Phillips, Karlye; Flowers, Bianca; Kershaw, Trace (Sexuality Research and Social Policy, 2025)
Keywords: Anxiety; Autonomy; Clinical psychology; Criminology; Domestic violence; Environmental health; HIV; Intimate partner violence; Medicine; Poison control; Political science; Population; Psychiatry; Psychology; Reproductive health; Sexual health; Sexual violence; Suicide prevention; Worry; dept.pch

Maternal prepregnancy body mass index and risk of preterm birth: the role of weight gain during pregnancy, race, and ethnicity - Sawadogo, Wendemi; Tsegaye, Medhin; Gizaw, Andinet; Newland, Hunter; Adera, Tilahun (American Journal of Perinatology, 2024)
Objective Preterm birth (PTB) is one of the leading causes of infant and neonatal mortality. Prepregnancy body mass index (BMI; kg/m2) has been linked to PTB but the evidence of this association by weight gain during pregnancy, race, and ethnicity is limited. This study aimed to assess the association between maternal prepregnancy BMI and PTB stratified by weight gain during pregnancy, race, and ethnicity. Study Design The U.S. natality data from 2017 to 2021 were used. In this analysis, we included mothers who had a live singleton birth and available data for prepregnancy BMI, gestational age at birth, weight gain during pregnancy, race, and ethnicity. Logistic regression models were used to assess the association between prepregnancy BMI categories and PTB stratified by weight gain during pregnancy, race, and ethnicity. Results A total of 17,311,509 singleton live births were included of which 1,393,889 (8.05 %) were PTBs. After adjusting for confounders, compared with normal prepregnancy BMI mothers (18.5–24.9), those with underweight BMI (<18.5) were at increased odds of PTB regardless of weight gain during pregnancy, race, and ethnicity. However, for mothers with a prepregnancy BMI above the normal weight (≥25), the association between prepregnancy BMI and PTB differs by weight gain during pregnancy, race, and ethnicity. Asian mothers with obesity II (35.0–39.9) had 93% (odds ratio [OR] = 1.93, 95% confidence interval [CI]: 1.62–2.30) increased odds of PTB for weight gain during pregnancy of 31 to 40 pounds. Their White, Hispanic, and Black counterparts experienced lower odds of PTB for similar weight gain during pregnancy (White: OR = 1.56, 95% CI: 1.51–1.60; Hispanic: OR = 1.48, 95% CI: 1.41, 1.54; and Black: OR = 1.22, 95% CI: 1.17–1.27). Conclusion Mothers with underweight BMI were at increased risk of PTB regardless of weight gain during pregnancy, race, and ethnicity. However, the association between high prepregnancy BMI and PTB varied by weight gain during pregnancy, race, and ethnicity. Key Points
Keywords: body mass index; dept.pch; ethnicity; obesity; peer-reviewed; pregnancy; preterm birth; race; weight gain during pregnancy

Black fathers' views on breastfeeding facilitators, barriers, and support services: Insights from a qualitative community-based participatory research study - Rios, Jasmine; Frieson, Tomeka; Ray, Natasha; Edwards, Doug; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2024)
Despite the persistence of breastfeeding racial and ethnic disparities in the United States, little is known about Black fathers' perceptions of breastfeeding and breastfeeding support services (e.g., maternity hospital-based care and lactation management care). This qualitative, community-based participatory research study reports Black fathers' perceptions of barriers and facilitators to breastfeeding, including the provision of breastfeeding support services in Connecticut. A focus group guide was co-developed with community partners and adapted from the Barrier Analysis Tool to identify breastfeeding facilitators, barriers, and service improvement areas. Four focus groups were conducted with 30 Black fathers who were Connecticut residents with a child under 3 years old. Qualitative data were analyzed using rapid template analysis involving deductive and inductive coding. We identified factors influencing breastfeeding and fathers' ability to support breastfeeding across all levels of the Socio-Ecological Model. Facilitators included high paternal breastfeeding knowledge, paternal breastfeeding involvement, parents' shared decision-making, extensive maternity hospital discharge support, ongoing breastfeeding support into the postnatal period, availability of community breastfeeding resources, and designated spaces for public breastfeeding. Barriers included low paternal breastfeeding knowledge, familial discouragement, insufficient prenatal breastfeeding education, exclusion of the father from breastfeeding support services, and stigma against breastfeeding in public. Understanding breastfeeding perceptions among members of a mother's support network, including their partners, is key for developing effective person- and family-centered breastfeeding education and counseling services that are well coordinated from the prenatal to postnatal periods with strong direct engagement from fathers.
Keywords: dept.pch; peer-reviewed

Racial and ethnic disparities in cancer occurrence and outcomes in rural United States: a scoping review - Njoku, Anuli; Sawadogo, Wendemi; Frimpong, Princess (Cancer Control, 2024)
BackgroundCancer is the second-leading cause of death in the United States. Most studies have reported rural versus urban and Black versus White cancer disparities. However, few studies have investigated racial disparities in rural areas.ObjectiveWe conducted a literature review to explore the current state of knowledge on racial and ethnic disparities in cancer attitudes, knowledge, occurrence, and outcomes in rural United States.MethodsA systematic search of PubMed and Embase was performed. Peer-reviewed articles published in English from 2004-2023 were included. Three authors independently reviewed the articles and reached a consensus.ResultsAfter reviewing 993 articles, a total of 30 articles met the inclusion criteria and were included in the present review. Studies revealed that underrepresented racial and ethnic groups in rural areas were more likely to have low cancer-related knowledge, low screening, high incidence, less access to treatment, and high mortality compared to their White counterparts.ConclusionUnderrepresented racial and ethnic groups in rural areas experienced a high burden of cancer. Improving social determinants of health may help reduce cancer disparities and promote health.
Keywords: dept.pch; peer-reviewed

Environmental Injustice and Electronic Waste in Ghana: Challenges and Recommendations - Njoku, Anuli; Agbalenyo, Martin; Laude, Janaya; Ajibola, Taiwo Folake; Attah, Mavis Asiwome; Sarko, Samuel Bruce (International Journal of Environmental Research and Public Health, 2023)
Electronic waste (e-waste) or discarded electronic devices that are unwanted, not working, or have reached their end of life pose significant threats to human and environmental health. This is a major concern in Africa, where the majority of e-waste is discarded. In the year 2021, an estimated 57.4 million metric tons of e-waste were generated worldwide. Globally, COVID-19 lockdowns have contributed to increased e-waste generation. Although Africa generates the least of this waste, the continent has been the dumping ground for e-waste from the developed world. The flow of hazardous waste from the prosperous ‘Global North’ to the impoverished ‘Global South’ is termed “toxic colonialism”. Agbogbloshie, Ghana, an e-waste hub where about 39% of e-waste was treated, was listed among the top 10 most polluted places in the world. The discard of e-waste in Ghana presents an issue of environmental injustice, defined as the disproportionate exposure of communities of color and low-income communities to pollution, its associated health and environmental effects, and the unequal environmental protection provided through policies. Despite the economic benefits of e-waste, many civilians (low-income earners, settlers, children, and people with minimal education) are exposed to negative health effects due to poverty, lack of education, and weak regulations. We critically examine the existing literature to gather empirical information on e-waste and environmental injustice. Comprehensive policies and regulations are needed to manage e-waste locally and globally.
Keywords: dept.pch; peer-reviewed

Utilizing Local Professional Association Chapters as Pathways for Leadership Development - Batista, Nicole; Risisky, Deb; Lutz, Tara M.; Clinesmith, Ellen; Morgan, Jahkeeva (Health Promotion Practice, 2024)
In 2019, there was no entity specifically dedicated to health promotion and education practitioners in Connecticut or New England. This made it difficult for health promotion practitioners and students to network, collaborate, and engage in professional development. The purpose of this article is to share our experiences developing the new Connecticut Chapter of the Society for Public Health Education (CT SOPHE), including how we leveraged student interns during the first two years to promote organizational growth. To build our membership, it was important to determine who would be interested in joining CT SOPHE and so we focused on three groups: the current workforce/professionals, future workforce/students, and future leaders/interns. Over the course of these two years, three interns were recruited to help with creating a needs assessment (MPH student) and program development (two BS students); the organization was established by an MPH student as her internship project. Three former interns share how their experience working with the CT SOPHE board has helped them develop crucial leadership skills early in their careers. Embedding student interns into the framework and operations of CT SOPHE demonstrates an intentional and strategic commitment to the sustainability of both the organization and the workforce.
Keywords: dept.pch; peer-reviewed

Understanding food insecurity among collegiate athletes: a qualitative study at a public university in New England - Anziano, Jennifer; Zigmont, Victoria A. (Journal of Athletic Training, 2024)
Context: Authors of previous research at a public university in New England, where the current study takes place, showed that approximately one-third of undergraduate students have experienced some aspect of food insecurity. More recent investigators at this university revealed that students who were members of a sport team were 4 times more likely to be food insecure than their peers who were not on a sport team. The estimated prevalence of student-athlete food insecurity from other previous research studies ranged from 14% to 32%. Objective: To understand the contributing factors to food insecurity among collegiate athletes. Design: Qualitative study. Setting: A public university in New England. Patients or Other Participants: Data are presented for 10 collegiate athletes who experienced some level of food insecurity according to the United States Department of Agriculture Six-Item Short Form. Data Collection and Analysis: Data were collected using a brief demographic questionnaire and semistructured interviews. Results: Contributing factors were a lack of time, special dietary needs, limited campus dining options, and limited access to transportation or kitchens. Coping strategies were managing time and resources, buying cheaper foods, and skipping meals. Food insecurity negatively affected students' athletic performance. The athletes struggled to balance their athletic and academic schedules and obtain a diet that allowed them to meet their performance goals. Conclusions: Additional and innovative programming is needed to support food-insecure student-athletes. © by the National Athletic Trainers' Association, Inc.
Keywords: academic performance; athletic performance; dept.pch; diet; nutrition; open-access; peer-reviewed

Perceptions of racial-ethnic inequities in COVID-19 healthcare and willingness to receive the COVID-19 vaccine - Sherchan, J.S.; Fernandez, J.R.; Njoku, A.; Brown, T.H.; Forde, A.T. (Epidemiology, 2024)
Background: Perceptions of the US healthcare system can impact individuals' healthcare utilization, including vaccination intentions. This study examined the association between perceived racial-ethnic inequities in COVID-19 healthcare and willingness to receive the COVID-19 vaccine. Methods: This study used data from REACH-US, a nationally representative online survey of a large, diverse sample of U.S. adults (N=5145 January 26, 2021-March 3, 2021). Confirmatory factor and regression analyses examined a latent factor of perceived racial-ethnic inequities in COVID-19 healthcare, whether the factor was associated with willingness to receive the COVID-19 vaccine, and whether associations varied across racial-ethnic groups reported as probit estimates (B) and 95% confidence intervals (CIs). Results: Perceived racial-ethnic inequities in COVID-19 healthcare were highest among Black/African American adults (mean latent factor score: 0.65 ± 0.43) and lowest among White adults (mean latent factor score: 0.04 ± 0.67). Black/African American (B = -0.08; 95% CI = -0.19, 0.03) and Native Hawaiian/Pacific Islander (B = -0.08; 95% CI = -0.23, 0.07) adults who perceived greater racial-ethnic inequities in COVID-19 healthcare were less willing than participants who perceived lower inequities. In contrast, American Indian/Alaska Native (B = 0.15; 95% CI = -0.01, 0.30), Asian (B = 0.20; 95% CI = 0.08, 0.31), Hispanic/Latino (English language preference) (B = 0.22; 95% CI = 0.01, 0.43), Multiracial (B = 0.23; 95% CI = 0.09, 0.36), and White (B = 0.31; 95% CI = 0.19, 0.43) adults who perceived greater racial-ethnic inequities in COVID-19 healthcare were more willing to receive the COVID-19 vaccine than participants perceiving higher inequities. Conclusions: Greater perceived racial-ethnic inequities in COVID-19 healthcare were associated with less willingness to receive the COVID-19 vaccine among Black/African American and Native Hawaiian/Pacific Islander adults. © 2024 Lippincott Williams and Wilkins. All rights reserved.
Keywords: COVID-19; COVID-19 Vaccine; Ethnicity; Health inequities; Healthcare disparities; Healthcare system; Race; dept.pch; open-access; peer-reviewed

Intentions to create green start-ups for collection of unwanted drugs: an empirical study - Njoku, A.; Mouloudj, K.; Bouarar, A.C.; Evans, M.A.; Asanza, D.M.; Mouloudj, S.; Bouarar, A. (Sustainability (Switzerland), 2024)
Drug waste poses a real threat to human health and the environment. Therefore, recycling and sustainability scholars have recently sought practical solutions to the drug waste problem. Furthermore, several governments have made significant efforts to reduce the negative effects of waste, such as establishing programs to take back unwanted drugs (expired and unused) for recycling (i.e., drug reuse or drug redispersing). However, many of these programs have failed to achieve their goals. In this context, it is expected that creating green start-ups to collect unwanted drugs will contribute to solving this problem. Accordingly, this study aims to investigate the antecedents of intentions to create green start-ups for collecting unwanted drugs. To this end, the authors integrate start-up self-efficacy and drug waste collection-related knowledge constructs into the theory of planned behavior (TPB). Using a self-administered paper questionnaire and relying on a convenience sample, data were collected from 328 students in six Algerian universities. A hierarchical multiple regression was conducted to test the proposed study model. Theresults revealed that perceived behavioral control (PBC) (β = 0.187, p < 0.001), attitudes (β = 0.182, p = 0.002), start-up self-efficacy (β = 0.169, p = 0.001), drug waste collection-related knowledge (β = 0.161, p < 0.001), and subjective norms (β = 0.088, p < 0.05) have a positive significant effect on the intention to create a start-up to collect unwanted drugs. In conclusion, this paper contributes to reducing drug waste by investigating the drivers of intention to create green start-ups for collecting unwanted drugs. Therefore, our study is expected to provide valuable insights for hospitals, pharmacies, pharmaceutical manufacturers, environmental protection associations, and stakeholders interested in reverse logistics. © 2024 by the authors.
Keywords: circular economy; dept.pch; expired drugs; green entrepreneurship; medication disposal; peer-reviewed; pharmaceutical waste; recycling; sustainability; theory of planned behavior; unused drugs; waste management knowledge

Nursing student perceptions of racism and health disparities in the United States: A critical race theory perspective - Costa, M.; Griswold, M.K.; Canty, L. (Nursing Outlook, 2024)
Background: Limited research has been done on nursing students’ awareness of racial disparities and their readiness to address bias and racism in clinical practice. Purpose: This study investigated nursing students' perceptions of how racial disparities affect health outcomes, including maternal outcomes, in the United States. Methods: Interpretive description was used and supported by the critical race theory as a framework to guide the data collection, analysis, and interpretation to understand participants’ perceptions surrounding racism and health disparities. Discussion: Nurse educators should guide students to look beyond individual behavioral and risk factors and consider systemic issues as a leading contributors to health disparities. Conclusion: The most critical finding was the lack of participants’ understanding of systemic racism and its impact on health disparities. While they often attributed racial disparities to low socioeconomic status and lack of education, they did not understand the relationships between social determinants of health and systemic racism. © 2024
Keywords: Maternal health outcomes; Nursing education; Racial disparities; Student perceptions; dept.pch; peer-reviewed

Rural America and Coronavirus Epidemic: Challenges and Solutions - Ameh, Governor G.; Njoku, Anuli; Inungu, Jeff; Younis, Mustafa (European Journal of Environment and Public Health, 2020)
There are emerging concerns about the preparedness of rural communities in the United States in the face of the 2019 novel coronavirus (called SARS-CoV-2, causing the disease COVID-19) considering the existing disparities across the social determinants of health between rural and urban Americans. Taking into account the current exponential rate of spread of the coronavirus, this article critically examines the risk facing the 60 million Americans living in rural areas, discusses possible solutions pertaining to rural COVID-19 prevention, and examines measures to consider to prepare for this epidemic before it reaches rural areas.
Keywords: dept.pch; peer-reviewed

Anxiety and Depression among Breast Cancer Patients Undergoing Treatment in Ghana - Kyei, K. A.; Oswald, J. W.; Njoku, A. U.; Kyei, J. B.; Vanderpuye, V.; Tschida, P. (African Journal of Biomedical Research, 2020)
Breast cancer patients undergoing radiotherapy often experience severe levels of anxiety and depression within the African context. There is a gap in the research literature from Africa, particularly Ghana, with few studies focusing on depression among patients undergoing radiation treatment. The purpose of the study was to find various interventions for depression and anxiety among breast cancer patients in Ghana. A mixed method study examined breast cancer patients undergoing radiotherapy and their responses through a concurrent triangulation involving an interview with selected professional and a detailed patient survey. In all, 100 patients between the ages of 20-89 completed a questionnaire and individual interviews were held with 6 professionals with a minimum of 5 years of work experience. Themes were generated through open coding of the interview data, while multiple regression was performed to determine the relationship between depression and anxiety with the independent variables. In all, 89% had no family history of breast cancer, and the majority (55%) had the disease duration of one to three years. Almost 95% of patients with breast cancer had anxiety and depression in different categories. This included hair loss, discolored finger nails, cost of treatment, and fear of the unknown. Age and monthly income of patients were statistically significant in predicting the anxiety and depression among the patients. Coping mechanisms are essential for all patients undergoing treatment. This study’s implications will lead to positive change when all stakeholders assist in implementing measures to promote coping strategies for breast cancer patients in Ghana.
Keywords: Anxiety; coping; depression; dept.pch; experience; intervention; peer-reviewed

Cancers in Rural Areas in the United States - Njoku, A.; Wakeel, F. (Foundations of Rural Public Health in America, 2021)
Foundations of Rural Public Health in America spans a wide variety of important issues affecting rural public health, including consumer and family health, environmental and occupational health, mental health, substance abuse, disease prevention and control, rural health care delivery systems, and health disparities. Divided into five sections, the book covers understanding rural communities, public health systems and policies for rural communities, health disparities in rural communities and among special populations, and advancing rural health including assessment, planning and intervention. Written by a multidisciplinary team of experienced scholars and practitioners, this authoritative text comprehensively covers rural health issues today.
Keywords: Medical / Public Health; dept.pch

Environmental health disparities and maternal and child health: applying the life course approach - Wakeel, Fathima; Njoku, Anuli (Handbook of Social Sciences and Global Public Health, 2023)
Mounting evidence suggests that differential environmental exposures significantly contribute to a wide range of population health disparities. Adopting a life course approach to maternal and child health enables readers to uncover the mechanisms by which prenatal and early life environmental exposures potentially shape both short- and long-term physical and mental health outcomes. This chapter applies the life course approach to explore the adverse influences of environmental risk factors on maternal and child health. The following four case studies will be discussed: (1) the pervasive impacts of secondhand smoke; (2) the deleterious effects of lead exposure; (3) the development of asthma; and (4) the potential origins of autism spectrum disorder. The chapter also provides recommendations for programmatic and policy interventions to reduce the prevalence of four salient environmental hazards, including secondhand smoke, lead, air pollution, and pesticides, as well as proposed future directions in research regarding these exposures.
Keywords: Asthma; Autism spectrum disorder; Environmental health justice; Health equity; Lead exposure; Life course approach; Maternal and child health; Secondhand smoke exposure; dept.pch

Study plans and programs supporting geriatric dentistry teaching in Cuba: An update - Asanza, D.M.; Herrera, I.A.R.; Njoku, A.; Puig, A.C.R.; Mouloudj, F.; Capote, I.G.; Maupome, G. (Geriatric Dentistry in the Age of Digital Technology, 2023)
The aging population in the world constitutes one of the greatest challenges of the 21st century across social sectors; dental education is no exception. This review explored the status of geriatric dentistry teaching in Cuba and contrasted it with examples from international curricula and programs. Google Scholar, PubMed, Wiley, and Scielo databases were used to search for articles that address geriatric dentistry topics, focusing on undergraduate curricular issues and the management of postgraduate specialization. The findings highlight the need to update curricula and programs for dentistry studies in Cuba to improve the quality of dental care for the aging population. The evolution of training future Cuban graduates aims to meet the healthcare needs of older adults while preserving their quality of life. Additionally, the incorporation of new information and communication technologies has been observed during this process. © 2024, IGI Global. All rights reserved.
Keywords: dept.pch

Environment injustice and public health - Njoku, Anuli U.; Sampson, Natalie R. (Handbook of Social Sciences and Global Public Health, 2023)
Globally, air pollution accounts for approximately one in eight deaths, and diarrheal diseases account for one in nine child deaths annually. Lead exposure contributes to concerns of heart disease, stroke, and developmental intellectual disability. Further, across the world, nearly 23 million people are displaced by extreme weather events each year, which have been exacerbated by climate change and contribute to physical and mental health implications for entire communities. These and many other environmentally related experiences and their subsequent health outcomes are not experienced equally by race, ethnicity, or income, with Black, Brown, and Indigenous communities and low-income communities repeatedly experiencing the heaviest of burdens. Due to a variety of historic and contemporary policy and planning decisions, these patterns of environmental injustice persist on local, national, and global scales. In response, environmental justice (EJ) is a social movement, as well as a belief that people of all backgrounds deserve access to clean air and water and a healthy community in which to thrive. This chapter heavily focuses on the USA and its environmental health inequities, policies, and historic EJ movement. However, in our globalized society, EJ is a global issue that must be addressed as such by the field of public health.
Keywords: Cumulative impacts; Environmental justice; Health equity; Social determinants of health; Systemic racism; dept.pch

COVID-19, housing, and environmental injustice - Njoku, Anuli; Marcelin, Joseph (Hygiene, 2023)
Keywords: dept.pch

Covid-19 and environmental racism - Njoku, Anuli; Marcelin, Joseph (Springer eBooks, 2023)
Keywords: dept.pch

Implementation Tools, Program Staff, and Budgets - Valdez-Barkwell, CM; Breny, J; Fagan, M; Roe, K (Health Program Planning, Implementation, and Evaluation, 2022)
Keywords: dept.pch

Spaces to heal: providing the table and seats - Njoku, Anuli; Evans, Marian (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Black, Indigenous, and People of Color (BIPOC) women faculty and administrators are breaking barriers, maintaining excellence, becoming award-winning scholars, and flourishing as experts in their fields. Still, they must survive while they thrive, grappling with insecurity, writer’s block, and imposter syndrome. Further examination prompts the realization that imposter syndrome may be a scapegoat for structural racism. Moreover, COVID-19 has created substantial health and financial tolls, fueled mental and emotional fatigue, and disrupted workplace productivity. These barriers caused by COVID-19 and structural racism inspire the courage to reassure, uplift, mentor, invite, and make collaborative spaces for BIPOC women to express feelings of vulnerability, unease, and, ultimately, hope. When seats are missing at the table, one can bring their own table and seats. In a field of often unforgiving critics, the authors provided underrepresented scholars the opportunity to promote authenticity and illuminate their voices. This chapter shares the authors’ reflections on being able to share the diverse and resilient perspectives of BIPOC women in academia.
Keywords: BIPOC women faculty; COVID-19; Imposter syndrome; Self-preservation; Sisterhood in the academy; dept.pch

Coping resources and self-care during COVID-19, police brutality, and social unrest - Njoku, Anuli (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
U.S. society has been gripped with dueling pandemics of racial and ethnic disparities in COVID-19 outcomes, highly publicized instances of police brutality against Black persons, and ensuing unrest to challenges these atrocities. In higher education, the rapid pivot response to COVID-19 with remote and virtual learning has also highlighted multiple levels of mental health trauma and disparities. There has also been vicarious trauma for Black women in academia who may have seen their family, friends, or loved ones reflected during increased media coverage of police brutality. This implores the need for effective strategies to mitigate these issues. This chapter discusses evidence-based strategies for Black women who navigate academia and teach during times of COVID-19 and social unrest. This chapter also proposes strategies for university leaders to consider alleviating cultural and racial gaps in the classroom or workplace and foster diversity and inclusion in academia.
Keywords: Academia; Black women; COVID-19; Higher education; Police brutality; Trauma; dept.pch

ACEing the Black Trauma of the COVID-19 Pandemic - Evans, Marian (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
When I first took the adverse childhood experiences (ACEs) quiz, I was overcome with the enormity of Black trauma contained in those ten questions. The quiz reflected my own story, as well as those of Black students, women, and families—traumas that were magnified by the impact of three pandemics: COVID-19, economic inequities, and systemic racism. The definition of trauma as “emotional responses to disastrous life events” like COVID-19 can have both short- and long-term health consequences throughout one’s lifespan. The impact of COVID-19 as Black trauma in my family will reverberate long after society heals from the last three years and moves toward living with COVID-19 symbiotically. It is imperative to recognize ACEs and their perpetual trauma to implement successful trauma-informed practices to counteract and undo the damaging effects of COVID-19 on our collective lives.
Keywords: ACEs quiz; Adverse childhood experiences; COVID-19; Trauma-informed practices; dept.pch

It’s a win-win: faculty-mentored research with students of color - Njoku, Anuli; Felix, Rochelle (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
In addition to fueling health disparities, the COVID-19 pandemic has exacerbated inequities among faculty of color. COVID-19 has also taken a dramatic toll on college students’ mental health, with evident racial disparities. Gender inequality in research productivity has also been revealed, with women submitting fewer papers compared to men. This pandemic has created an opportunity, of sorts, to promote academic and career success among women and students of color in academia. Research has shown that mentorship and research opportunities improve chances for success among students of color in higher education. Faculty members can also progress personally and professionally from such collaborations. Still, students of color are not equally given opportunities to collaborate with faculty on research. This chapter shares perspectives and strategies from Black women faculty and graduate students regarding faculty-student research to promote academic and career success among faculty and students of color in academia.
Keywords: COVID-19; Faculty-mentored research; Mentoring; Student research; Students of color; dept.pch

Giving Up Is Never an Option: Personal and Professional Development During COVID-19 - Felix, Rochelle (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
COVID-19 brought me challenges and opportunities. I lost important people in this pandemic but also accomplished a lot. COVID-19 gave me a chance to soul search, grow, and develop. I blossomed into the woman I have always wanted to be but could not find. During it all, I was awarded my undergraduate degree, got accepted to a graduate program, received a new job, and bought my first car. With every blessing came a challenge, including health problems. Still, I persevered. Opportunities continue to present themselves and I seize them. Professional successes included publishing an article, presenting at a state public health conference, being featured in my university’s annual newsletter, and nailing my dream job! I got to “See Me!”, a woman of color coming from another country, accomplishing so much in a short span of time. This chapter details a true testimony and how giving up is not an option.
Keywords: COVID-19; Graduate students; Mental health; Resilience; dept.pch

Navigating academia during COVID-19: perspectives and strategies from BIPOC women - Njoku, Anuli; Evans, Marian (Springer International Publishing, 2023)
Keywords: BIPOC faculty; Covid-19; Gender and Education; dept.pch; narrative inquiry; professional development; trauma

Modeling predictors of medication waste reduction intention in Algeria: extending the theory of planned behavior - Mouloudj, Kamel; Njoku, Anuli; Asanza, Dachel Martínez; Bouarar, Ahmed Chemseddine; Evans, Marian A.; Mouloudj, Smail; Bouarar, Achouak (International Journal of Environmental Research and Public Health, 2023)
COVID-19 caused an increase in the demand for medications, which led to an increase in pharmaceutical waste and there is no doubt that this contributes to environmental pollution. Hence, it became necessary to search for how to protect and improve the environment by encouraging the behavior of medication waste reduction. Accordingly, this study aims to investigate the factors affecting intentions to reduce medication waste. Considering this, we develop an extended theory of planned behavior (TPB) framework by incorporating the constructs of moral obligation, environmental awareness, and medication waste risk perception. Using the convenience sampling method and based on a self-administered questionnaire, a total of 225 usable responses were collected in five Algerian cities. The results showed that positive attitudes (β = 0.316, p < 0.001), moral obligation (β = 0.291, p < 0.001), environmental awareness (β = 0.227, p < 0.001), perceived behavior control (PBC) (β = 0.151, p = 0.001), greater perceived risks (β = 0.127, p < 0.001), and subjective norm (β = 0.096, p < 0.05) significantly and positively influence the medication waste minimization intention. Furthermore, our analyses revealed that the extended TPB model explained 73.40% of the intention variance. In conclusion, we have explored the intentions, and there may be a gap between intent and actual behavior. Therefore, we recommend future studies to examine the factors affecting the actual behavior of medication waste reduction and to investigate environmental ethics and religious commitment as predictors of waste reduction intentions.
Keywords: Africa; dept.pch; environmental health; environmental pollution; medication ecotoxicity; medication waste; moral obligation; peer-reviewed; perceived risk; pharmaceutical waste; theory of planned behavior; unused medications

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Shifting Sustainable Lifestyle Practices and Behaviour During Times of Pandemic Disruptive Change: Implications for on-Going Socio-Technical Transitions - Axon, Stephen; Lent, Talia; Njoku, Anuli (Energy Research & Social Science, 2023)
COVID-19 has extensively reshaped lifestyle practices, supply chain dynamics, and climate mitigation efforts. The resulting crises from the pandemic in relation to local and community sustainability practices have not yet been investigated in depth. There is a need to explore the individual characteristics and responses from rapid transitions of lifestyles at various scales. Analysing how the COVID-19 pandemic has shaped and altered sustainable living practices, and the motivations supporting them, has yet to be determined but is crucial to gain further insight to improve management responses to large-scale disruptive change. Presenting empirical findings from semi-structured interviews in New Haven County, Connecticut, this study elucidates the ways in which the lifestyles have been altered and how they responded while specifically highlighting the consequences for behavioural routines and sustainable lifestyle practices. As a result of lockdowns and pandemic mitigation responses, individual sustainability engagement fluctuated with participants shifting dietary, mobility, and energy and food consumption patterns. Specifically, participants emphasised substantial decrease in daily travel during initial phases of the pandemic alongside increased online shopping and energy use at home. Though changes to consumption practices were replaced former habits with unsustainable ones, individuals also noted how they co-opted the pandemic over time to pursue sustainable actions at home. As a macro-level ‘window of opportunity’ and disruptive change, this study illustrates how sustainable lifestyle practices were reshaped; some by choice, some by force, and some reflecting a forced choice. These findings have clear implications for the stability of maintaining sustainable practices influenced by landscape-level shocks.
Keywords: Behaviour change; COVID-19; Energy use; Food consumption; Social practices; Transport; dept.egm; dept.pch; peer-reviewed

Racial and Ethnic Disparities in Chronic Stress among Male Caregivers - Unson, Christine; Njoku, Anuli; Bernard, Stanley; Agbalenyo, Martin (International Journal of Environmental Research and Public Health, 2023)
Whereas research on caregiving is well documented, less is known about gender inequalities in caregiver stress, coping mechanisms, and health outcomes, all of which may vary by race, ethnicity, and socioeconomic status. This scoping review investigated racial and ethnic disparities using the Stress Process Model among male caregivers. Several databases were searched including Academic Search Premier, Medline Complete, APA PsycInfo, CINHAL, Google, ProQuest, and Web of Science. Included were peer-reviewed articles in English, published from 1990 to 2022. A total of nine articles fulfilled inclusion criteria. Most of the articles indicated that compared to White male caregivers, African American male caregivers provided more hours of care, assisted with more activities of daily living (ADLs) and instrumental activities of daily living (IADLs), and experienced more financial stress. In terms of coping style, one study found African American male caregivers, compared to White male caregivers, held negative religious beliefs. Another study showed that they were at a higher risk for stroke than their White counterparts. The search revealed a dearth of studies on racial disparities in stress, coping, and health outcomes among male caregivers. Further research is needed on the experiences and perspectives of male minority caregivers. © 2023 by the authors.
Keywords: African American males; aging; caregiver burden; caregiving; coping; dept.pch; health and aging; health disparities; intersectionality; male caregiver; masculinity; older adults; peer-reviewed

"Go with the flow": a qualitative description of infant feeding experiences among women with hiv in the united states - Pagano-Therrien, J.; Griswold, M.K.; Amoah, R.K. (The Journal of the Association of Nurses in AIDS Care : JANAC, 2023)
ABSTRACT: Breastfeeding affords numerous health benefits to mothers and children, but for women with HIV in the United States, avoidance of breastfeeding is recommended. Evidence from low-income countries demonstrates low risk of HIV transmission during breastfeeding with antiretroviral therapy, and the World Health Organization recommends exclusive breastfeeding and shared decision making about infant feeding options in low-income and middle-income countries. In the United States, gaps in knowledge exist surrounding the experiences, beliefs, and feelings of women with HIV surrounding infant feeding decisions. Undergirded by a framework of person-centered care, this study describes the experiences, beliefs, and feelings of women with HIV in the United States surrounding recommendations for breastfeeding avoidance. Although no participants reported consideration of breastfeeding, multiple gaps were identified with implications for the clinical care and counseling of the mother-infant dyad. Copyright © 2023 Association of Nurses in AIDS Care.
Keywords: dept.pch; peer-reviewed

Factors influencing the adoption of digital health apps: an extended technology acceptance model (TAM) - Mouloudj, Kamel; Bouarar, Ahmed Chemseddine; Asanza, Dachel Martínez; Saadaoui, Linda; Mouloudj, Smail; Njoku, Anuli U.; Evans, Marian A.; Bouarar, Achouak (Integrating Digital Health Strategies for Effective Administration, 2023)
Mobile health apps have been widely considered in the healthcare sector as innovative channels to reach patients and their families. Accordingly, the aim of the chapter was to investigate factors that influence the customers' adoption of digital health apps in Algeria. The authors adopted an extende...
Keywords: dept.pch

Exploring What Influences Heterosexual College Men and the Practice of Safe Sex: The Power of Stigma and Community - Breny, J.M.; Joseph, M.; Robledo, D.; Rondeau, D.; D’Haity, W.; Mucha, J.; Zapata, P. (Journal of Community Health, 2023)
The college student population is among the highest risk group for contracting sexually transmitted infections (STIs) such as gonorrhea, chlamydia, and HIV. Safe sex practices, which are intended to mitigate risks associated with sexually transmitted infections, are often negated in the population of heterosexual college students. Historically, research on safe sex practices has shown that the burden of behavior change and the focus on educational efforts historically fall onto the female population. There is little published on how safe sex education for males impacts attitudes and behaviors towards safe sex practices. This community-based participatory research (CBPR) project explored heterosexual college male attitudes and behaviors about safe sex responsibilities with the goal of creating effective health promotion messages to increase safer sex. The research team comprised almost entirely of undergraduate male students, which strengthened the design and translation of results to practice. A mixed methods design was employed utilizing both focus groups and surveys as data collection (n=121). Results showed that young men are still prioritizing pregnancy prevention over disease contraction and/or testing, and relying on female partners to initiate safe sex. Implications for health promotion practice efforts on college campuses include: male-led peer education programming and support and messaging around screening and prevention of STIs. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: CBPR; College health promotion; Condom use; HIV prevention; Peer education programs; STI prevention; dept.pch; peer-reviewed

Creating a Narrative for Change: Health Promotion Students’ Perspectives on the Power of Photovoice Research - De Leon, Breanna; Mahama, Fatawu; Raymond, Ashley; Palmer, Cheryl A; Breny, Jean M. (Health Promotion Practice, 2023)
The use of Critical Race Theory, Photovoice, and Community-Based Participatory Research has helped uncover the root causes of issues such as systemic racism in the fields of public health and health promotion. Often, we see studies using traditional research methods to investigate potential causal factors of disparities in minoritized communities report only quantitative data. While these data are imperative for understanding the severity of disparities, quantitative-only approaches cannot address nor can they improve the critical root causes of these disparities. As a team of BIPOC graduate students in public health, we conducted a community-based participatory research project using Photovoice methodology to explore inequities in Black and Brown communities exacerbated during the COVID-19 pandemic. The participatory nature of this research revealed cumulative challenges across the social determinants of health in New Haven and Bridgeport, Connecticut. It allowed us to engage in local-level advocacy to promote health equity as our findings illuminated the need for community-led and community-engaged action. Health and racial inequities cannot be effectively addressed if public health research and programming do not collaborate with the community to build community capacity, empowerment, and trust. We describe our experiences doing community-based participatory research to investigate inequities and provide reflections on their value for public health students. As responses to health inequities and disparities become more politically polarized in the United States, it is critical for public health and health education students to use research methodologies that elevate communities that have been historically marginalized and neglected. Together, we can catalyze equitable change.
Keywords: dept.pch; peer-reviewed

Listen to the whispers before they become screams: addressing black maternal morbidity and mortality in the united states - Njoku, Anuli; Evans, Marian; Nimo-Sefah, Lillian; Bailey, Jonell (Healthcare, 2023)
Black women in the United States (U.S.) disproportionately experience adverse pregnancy outcomes, including maternal mortality, compared to women of other racial and ethnic groups. Historical legacies of institutionalized racism and bias in medicine compound this problem. The disproportionate impact of COVID-19 on communities of color may further worsen existing racial disparities in maternal morbidity and mortality. This paper discusses structural and social determinants of racial disparities with a focus on the Black maternal mortality crisis in the United States. We explore how structural racism contributes to a greater risk of adverse obstetric outcomes among Black women in the U.S. We also propose public health, healthcare systems, and community-engaged approaches to decrease racial disparities in maternal morbidity and mortality.
Keywords: COVID-19; black maternal mortality; dept.pch; health disparities; intersectionality; morbidity; peer-reviewed; pregnancy; race/ethnicity; racism; social determinants of health; weathering framework

Undergraduate food insecurity, mental health, and substance use behaviors - Neal, Latasha; Zigmont, Victoria A. (Nutrition and Health, 2022)
Objective: Recent epidemiological research has found food insecurity to be a growing public health concern among college students. This study investigated food insecurity, mental health, and substance use behaviors among state university undergraduate students. Study Design: Cross-sectional survey. Methods: This was a secondary data analysis of the Student Health Survey. Undergraduate participants ( n = 589) completed the paper-based survey, which had an 84% response rate overall. Results: Approximately 38.5% of students were considered food insecure, 24.8% experiencing low food security, and 13.8% experiencing very low food security. Having a diagnosis of depression, experience of depressive symptoms, and marijuana use in the past 30 days were associated with food insecurity. Conclusion and Implications: Food insecurity is a serious health concern for college students. The results of this study indicate collocating food security and counseling services may enhance existing student resources to better support students facing food and nutrition insecurity, substance use, and depression.
Keywords: SCSU-student; dept.pch; dept.psy

The HPP Podcast: People, Places, Possibilities—Living & Reimagining Beyond the Page - Mata, Holly J.; Castle, Arden; Johnson, Chloe; Latz, Isabel; Castro, Justine Karla; Roe, Kathleen (Health Promotion Practice, 2022)
Keywords: dept.pch; peer-reviewed

Captive Market Pricing and Lack of Transportation: A Survey of Undergraduate Food Insecurity at a Public University in New England - Zigmont, V.A.; Anziano, J.; Schwartz, E.; Gallup, P. (American Journal of Health Promotion, 2022)
Purpose: The purpose of this study is to describe the prevalence of food insecurity among college students and its relationship to on-campus food purchasing patterns and barriers to eating a healthy and sufficient diet, including the relative cost of food items on campus compared to national chain grocery stores. Design: A campus-wide survey using stratified sampling among undergraduates and food audit. Setting: An urban public university in New England. Subjects: A total of 951 surveys completed by undergraduates. Measures: Demographic characteristics, behavioral factors and food security status (measured using the USDA 6-item short form) were collected. Method: Descriptive and multivariable analyses were conducted to describe differences between food insecure and food secure undergraduates. Results: Overall, 35% of undergraduates experienced food insecurity in the past year (response rate = 92%). Food insecure undergraduates had different on-campus purchasing patterns than their food secure counterparts. Food insecure students were more likely to report barriers to healthy eating on all measures, including prices (AOR= 8.12, P <.0001), to experience housing insecurity (AOR= 2.64, P =.001) and to report that transportation is a barrier to buying groceries (AOR= 1.63, P =.01). After multivariable adjustment, food insecure undergraduates had higher odds of being African American (AOR= 1.57, P =.031) or other races (more than 1 race) (AOR= 3.35, P =.002) compared to white undergraduates. Conclusions: Food insecure college students face a variety of barriers to healthy eating on campus, including high food pricing on campus and limited transportation options. Further research is needed to inform campus resource development, policies and programming focused on food insecurity prevention for college students. © The Author(s) 2022.
Keywords: college students; dept.pch; food insecurity; food prices; higher education; hunger; peer-reviewed; transportation

Barriers and facilitators to exclusive breastfeeding among Black mothers: A qualitative study utilizing a modified Barrier Analysis approach - Tran, Victoria; Reese Masterson, Amelia; Frieson, Tomeka; Douglass, Frankie; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2022)
Breastfeeding has health benefits for both infants and mothers, yet Black mothers and infants are less likely to receive these benefits. Despite research showing no difference in breastfeeding intentions by race or ethnicity, inequities in breastfeeding rates persist, suggesting that Black mothers face unique barriers to meeting their breastfeeding intentions. The aim of this study is to identify barriers and facilitators that Black women perceive as important determinants of exclusively breastfeeding their children for at least 3 months after birth. Utilizing a Barrier Analysis approach, we conducted six focus group discussions, hearing from Black mothers who exclusively breastfed for 3 months and those who did not. Transcripts were coded starting with a priori parent codes based on theory-derived determinants mapped onto the Socioecological Model; themes were analysed for differences between groups. Facilitators found to be important specifically for women who exclusively breastfed for 3 months include self-efficacy, lactation support, appropriate lactation supplies, support of mothers and partners, prior knowledge of breastfeeding, strong intention before birth and perceptions of breastfeeding as money-saving. Barriers that arose more often among those who did not exclusively breastfeed for 3 months include inaccessible lactation support and supplies, difficulties with pumping, latching issues and perceptions of breastfeeding as time-consuming. Lack of access to and knowledge of breastfeeding laws and policies, as well as negative cultural norms or stigma, were important barriers across groups. This study supports the use of the Socioecological Model to design multicomponent interventions to increase exclusive breastfeeding outcomes for Black women.
Keywords: barrier analysis; breastfeeding; dept.csc; dept.pch; focus group; peer-reviewed; public health; qualitative methods; social factors; sociocultural analyses

Comparing Environmental Policies to Reduce Pharmaceutical Pollution and Address Disparities - Desai, Meghana; Njoku, Anuli; Nimo-Sefah, Lillian (International Journal of Environmental Research and Public Health, 2022)
Pharmaceutical products, including active pharmaceutical ingredients and inactive ingredients such as packaging materials, have raised significant concerns due to their persistent input and potential threats to human and environmental health. Discourse on reducing pharmaceutical waste and subsequent pollution is often limited, as information about the toxicity of pharmaceuticals in humans is yet to be fully established. Nevertheless, there is growing awareness about ecotoxicity, and efforts to curb pharmaceutical pollution in the European Union (EU), United States (US), and Canada have emerged along with waste disposal and treatment procedures, as well as growing concerns about impacts on human and animal health, such as through antimicrobial resistance. Yet, the outcomes of such endeavors are often disparate and involve multiple agencies, organizations, and departments with little evidence of cooperation, collaboration, or oversight. Environmental health disparities occur when communities exposed to a combination of poor environmental quality and social inequities experience more sickness and disease than wealthier, less polluted communities. In this paper, we discuss pharmaceutical environmental pollution in the context of health disparities and examine policies across the US, EU, and Canada in minimizing environmental pollution.
Keywords: dept.pch; disparities; environmental policies; peer-reviewed; pharmaceutical pollution; pharmaceutical waste

Research engagement in a virtual world: Strategies for maintaining the power and impact of photovoice research online - Breny, J.M.; McMorrow, S.L. (Health promotion practice, 2022)
When our photovoice research intersected with the COVID-19 pandemic, we were thrust into a new world of adapting the method in the virtual environment. Between both authors, we had over two decades of experience implementing photovoice. However, that involved tried and true methods of working face to face and side by side with people in community-based settings. This article describes lessons learned from two virtual photovoice projects. One involved pivoting from a project already well underway in person to online and the other was designed for virtual implementation since that was the only option available. Key considerations discussed are navigating our institutional review boards, adapting project management, building community online, and sharing results and advocacy for social change. Dilemmas and key decisions in each of these areas are described for practitioners and community-based researchers who need or seek to transition their photovoice research to the virtual environment. Practical tips and strategies for implementation are described and offered to photovoice researchers.
Keywords: dept.pch; peer-reviewed

We are family: Effects of a relationship-strengthening prevention intervention on parenting behaviors among black and latino adolescent couples - Diaz, V.R.; Albritton, T.; Katague, M.; Dancy, V.; Breny, J.M.; Kershaw, T. (Journal of Family Issues, 2022)
Relationship strain or dissolution between new parents can affect the co-parenting relationship and parenting engagement. The purpose of this study was to evaluate the effect of a relationship-strengthening intervention on parenting behaviors among adolescent couples. Data from a pilot randomized control trial conducted with predominantly Black and Latino couples were analyzed using repeated measures analysis of variance. Observed intervention * time effects and intervention * time * gender effects were not statistically significant, but had small to moderate effect sizes. Intervention couples demonstrated increased parenting sense of competence compared to control couples. Gender differences in intervention effects were observed for both parenting experiences and parenting engagement. Given the pilot nature of the study, these findings provide preliminary evidence of the effectiveness of this couple-based intervention for improving parenting outcomes. Future research should assess the intervention in a larger sample and leverage technology-based approaches as methods for content delivery. © The Author(s) 2022.
Keywords: dept.pch; peer-reviewed

Black women faculty and administrators navigating COVID-19, social unrest, and academia: Challenges and strategies - Njoku, A.; Evans, M. (International Journal of Environmental Research and Public Health, 2022)
Black women faculty and administrators in the United States are tackling a force of socioeconomic and racial disparities, emotional tolls and invisible burdens within academia, political turmoil, social unrest, and public health crises. COVID-19 has added an additional layer related to work responsibilities, the overall well-being of Black women faculty and administrators and the diverse students they encounter, and management of work and home responsibilities. This paper discusses perspectives and evidence-based strategies regarding Black women faculty and administrators who navigate academia and teach during times of COVID-19 and social unrest. We also outline strategies for university leaders to mitigate cultural and racial gaps in the classroom or workplace and foster diversity and inclusion in academia. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: African American; African Americans; Article; COVID-19; Faculty; Female; Humans; Racism; SARS-CoV-2; United States; coronavirus disease 2019; dept.pch; epidemiology; evidence based practice; female; health care planning; health disparity; human; peer-reviewed; racism; social determinants of health; tertiary education; university

COVID-19 and Health Disparities: Opportunities for Public Health Curriculum Enhancement - Njoku, Anuli (COVID-19 and Higher Education in the Global Context, 2022)
COVID-19, the pandemic of highly contagious respiratory disease, presents a global public health emergency. The COVID-19 pandemic has increased awareness of the role of public health and its professionals in responding to the pandemic. Racial and ethnic minority groups in the United States are more likely to contract and die from COVID-19 versus Whites, highlighting health disparities. Higher education schools and programs in public health can help prepare students to address this global pandemic through expanded curriculum on social determinants of health disparities in COVID-19 outcomes, teachings on implicit bias and anti-racism, interprofessional education, and practice-based learning. Moreover, eliminating health disparities is a leading public health priority in the United States and can help attain the World Health Organization goal of achieving health equity. This chapter highlights the need for public health curriculum that outlines strategies to address racial and ethnic disparities in COVID-19 to prepare and motivate a future healthcare workforce. How to cite this chapter: Njoku, A. (2022). COVID-19 and health disparities opportunities for public health curriculum enhancement. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 139-153). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/
Keywords: dept.pch; ⛔ No DOI found

COVID-19 Vaccine Acceptance and Access Among Black and Latinx Communities - Balasuriya, Lilanthi; Santilli, Alycia; Morone, Jennifer; Ainooson, Jessica; Roy, Brita; Njoku, Anuli; Mendiola-Iparraguirre, Andrea; O’Connor Duffany, Kathleen; Macklin, Bernard; Higginbottom, Jackson; Fernández-Ayala, Celina; Vicente, Genesis; et al. (JAMA Network Open, 2021)
Black and Latinx communities have faced disproportionate harm from the COVID-19 pandemic. Increasing COVID-19 vaccine acceptance and access has the potential to mitigate mortality and morbidity from COVID-19 for all communities, including those most impacted by the pandemic.To investigate and understand factors associated with facilitating and obstructing COVID-19 vaccine access and acceptance among Black and Latinx communities.This community-partnered qualitative study conducted semistructured, in-depth focus groups with Black and Latinx participants from March 17 to March 29, 2021, using a secure video conferencing platform. Participants were recruited through emails from local community-based organizations, federally qualified health centers, social service agencies, the New Haven, Connecticut, Health Department, and in-person distribution of study information from community health workers. A total of 8 focus groups were conducted, including 4 in Spanish and 4 in English, with 72 participants from a diverse range of community roles, including teachers, custodial service workers, and health care employees, in New Haven, Connecticut. Data were analyzed from March 17 to July 30, 2021.Interviews were audio-recorded, transcribed, translated, and analyzed using an inductive content analysis approach. Themes and subthemes were identified on the acceptability and accessibility of the COVID-19 vaccine among participants who identified as Black and/or Latinx.Among 72 participants, 36 (50%) identified as Black, 28 (39%) as Latinx, and 8 (11%) as Black and Latinx and 56 (78%) identified as women and 16 (22%) identified as men. Participants described 3 major themes that may represent facilitators and barriers to COVID-19 vaccinations: pervasive mistreatment of Black and Latinx communities and associated distrust; informing trust via trusted messengers and messages, choice, social support, and diversity; and addressing structural barriers to vaccination access.The findings of this qualitative study may impact what health care systems, public health officials, policy makers, health care practitioners, and community leaders can do to facilitate equitable uptake of the COVID-19 vaccine. Community-informed insights are imperative to facilitating COVID-19 vaccine access and acceptance among communities hardest hit by the pandemic. Preventing the further widening of inequities and addressing structural barriers to vaccination access are vital to protecting all communities, especially Black and Latinx individuals who have experienced disproportionate death and loss from COVID-19.
Keywords: Adolescent; Adult; African American; African Americans; Article; Black person; COVID-19 Vaccines; Connecticut; Female; Focus Groups; Health Services Accessibility; Hispanic; Hispanic Americans; Humans; Male; Middle Aged; Patient Acceptance of Health Care; SARS-CoV-2 vaccine; South and Central America; Trust; Young Adult; adolescent; adult; aged; community; content analysis; controlled study; coronavirus disease 2019; dept.pch; e-mail; employment; female; health auxiliary; health behavior; health care access; health care delivery; health care personnel; health care system; health center; health disparity; human; information processing; male; medical information; middle aged; outcome assessment; pandemic; patient attitude; peer-reviewed; public health service; qualitative research; risk factor; semi structured interview; social support; social worker; teacher; trust; vaccination; videoconferencing; young adult

Changing the narrative: Structural barriers and racial and ethnic inequities in COVID-19 vaccination. - Njoku, Anuli; Joseph, Marcelin; Felix, Rochelle (International journal of environmental research and public health, 2021)
The COVID-19 pandemic has disproportionately affected racial and ethnic minority groups in the United States. Although a promising solution of the COVID-19 vaccination offers hope, disparities in access again threaten the health of these communities. Various explanations have arisen for the cause of disparate vaccination rates among racial and ethnic minorities, including discussion of vaccine hesitancy. Conversely, the role of vaccine accessibility rooted in structural racism as a driver in these disparities should be further explored. This paper discusses the impact of structural barriers on racial and ethnic disparities in COVID-19 vaccine uptake. We also recommend public health, health system, and community-engaged approaches to reduce racial disparities in COVID-19 disease and mortality. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: African American; Article; Black person; COVID-19; COVID-19 Vaccines; Coronavirus; Ethnic Groups; Health Status Disparities; Healthcare Disparities; Humans; Latino people; Minority Groups; Pandemics; SARS-CoV-2; SARS-CoV-2 vaccine; United States; Vaccination; access to computer; access to information; black population; communication barrier; coronavirus disease 2019; dept.pch; ethnic disparity; ethnic group; ethnic minority; health care access; health care disparity; health care system; health disparity; health literacy; health services; human; immigrant; infection prevention; internet access; language ability; mass immunization; minority group; mortality; outcome assessment; pandemic; peer-reviewed; public access; public health service; race difference; racial disparity; racism; social behavior; social determinants of health; social inequality; structural barrier; traffic and transport; vaccination

Exposure to Di-2-ethylhexyl phthalate (DEHP) and infertility in women, NHANES 2013-2016. - Trnka, Brittany; Polan, Maya; Zigmont, Victoria A. (Reproductive toxicology (Elmsford, N.Y.), 2021)
Di-2-ethylhexyl phthalate (DEHP) exposure is widespread in the general population and previous research has suggested that it contains endocrine-disrupting properties that can adversely affect the reproductive health system. The objective of this study was to use the 2013–2016 National Health and Nutrition Examination Survey (NHANES) data to assess the potential association between DEHP exposure and infertility in women. Using a nationally representative, cross-sectional study design, we used multiple logistic regression to measure the association of urinary metabolites of DEHP with self-reported history of infertility among women. Four metabolites of DEHP were examined: mono(2-ethylhexyl)phthalate (MEHP), mono(2-ethyl-5-hydroxy-hexyl)phthalate (MEHHP), mono(2-ethyl-5-oxy-hexyl) phthalate (MEOHP), and mono(2-ethyl-5-carboxy-pentyl)phthalate (MECPP). These metabolites were calculated into a molar sum of DEHP (∑DEHP) and split into quartiles for analysis. After adjusting for age and race, ∑DEHP was associated with increased odds of infertility for the second quartile (AOR = 2.35, 95% CI [1.24,4.44], p = 0.01) and third quartile (AOR = 2.83, 95% CI [1.57, 5.10], p ¡ 0.01) when compared to the first quartile (reference). The adjusted OR for the highest quartile of ∑DEHP found no association and it was not statistically significant (AOR = 0.99, 95 %CI [0.57, 1.73], p = 0.98). The findings of this study add to the already complex existing literature on phthalate exposure and infertility. These findings warrant further population-based cohort studies on phthalate exposure and their relationship to infertility in humans. © 2021 Elsevier Inc.
Keywords: Adult; Article; Cross-Sectional Studies; Diethylhexyl Phthalate; Endocrine Disruptors; Environmental Exposure; Environmental Pollutants; Female; Humans; Infertility; Male; Middle Aged; Nutrition Surveys; Phthalic Acids; Young Adult; adult; cohort analysis; controlled study; cross-sectional study; dept.pch; drug urine level; electrospray mass spectrometry; endocrine disruptor; environmental exposure; exposure; female; female infertility; high performance liquid chromatography; human; infertility; limit of detection; major clinical study; male; middle aged; mono(2 ethyl 5 carboxy pentyl)phthalate; mono(2 ethyl 5 hydroxy hexyl)phthalate; mono(2 ethyl 5 oxy hexyl)phthalate; mono-(2-ethylhexyl)phthalate; nutrition; peer-reviewed; phthalic acid; phthalic acid 2 ethylhexyl monoester; phthalic acid bis(2 ethylhexyl) ester; phthalic acid derivative; pollutant; questionnaire; sensitivity analysis; toxicity; unclassified drug; young adult

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Book Review: FrielSharon. Climate Change and the People's Health. New York, NY: Oxford University Press, 2019. $29.95. pp. 232. ISBN: 9780190492731. - Jung, Betty C. (World Medical & Health Policy, 2021)
Keywords: Health Policy; book.review; dept.pch

Collaborating With Parks and Recreation Departments to Address Youth Health - Risisky, Deb; MacGregor, James (Health Promotion Practice, 2021)
Adolescence is an important time for addressing health, including mental health, obesity, substance use, and food insecurity. As the myriad health and wellness needs of community members expands, it becomes increasingly difficult for one profession alone to address these needs. The park and recreation field was founded to address the health and wellness needs of people, and much of their programming is focused on youth. Thus, municipal park and recreation departments are becoming increasingly involved in collaborative partnerships with other health-serving agencies within their community. This study explored park and recreation directors’ experiences in collaborating with health agencies to better address health and wellness factors that affect the youth in their communities. This phenomenological qualitative study employed in-depth interviews with park and recreation directors and used thematic analysis. Nine interviews were conducted from four of the six New England states. The most common health concern seen by the directors was mental health, primarily behavioral health challenges. Parks and recreation collaboration with public health organizations ranged from none to close collaborations; directors regularly spoke about wanting to strengthen their collaborations. Public health and park and recreation staff have similar challenges with staffing and resources; additionally, they have complimentary skills with regard to planning and implementing health-related programs. For that reason, creating purposeful collaborative partnerships between public health agencies and park and recreation departments, focused on measurable outcomes, may increase benefits to the health of youth in a community.
Keywords: adolescent health; collaboration; dept.pch; dept.rec; mental health; multisector; park and recreation; peer-reviewed; physical activity; prevention; trauma

Barriers and Motivators to Opioid Treatment Among Suburban Women Who Are Pregnant and Mothers in Caregiver Roles. - Boeri, Miriam; Lamonica, Aukje K; Turner, Jeffrey M; Parker, Amanda; Murphy, Grace; Boccone, Carly (Frontiers in psychology, 2021)
Women of childbearing age who misuse opioids are a particularly vulnerable population, and their barriers to treatment are unique because of their caregiver roles. Research on treatment for opioid use generally draws from urban and rural areas. This study fills a gap in research that focuses on barriers and motivators to opioid treatment in suburban areas. The aim of this study was to give voice to suburban pregnant women and mothers caring for children while using opioids. Ethnographic methods were used for recruitment, and 58 in-depth interviews were analyzed using a modified grounded theory approach. Barriers to medication-assisted treatment (MAT) included stigma, staff attitudes, and perceptions the women had about MAT treatment. Barriers associated with all types of treatment included structural factors and access difficulties. Relationships with partners, friends, family, and providers could be barriers as well as motivators, depending on the social context of the women's situation. Our findings suggest increasing treatment-seeking motivators for mothers and pregnant women by identifying lack of resources, more empathetic consideration of social environments, and implementing structural changes to overcome barriers. Findings provide a contemporary understanding of how suburban landscapes affect mothers' treatment-seeking for opioid dependence and suggest the need for more focus on emotional and structural resources rather than strict surveillance of women with opioid dependence who are pregnant or caring for children. Copyright © 2021 Boeri, Lamonica, Turner, Parker, Murphy and Boccone.
Keywords: dept.pch; peer-reviewed

Correlates of Strength and Balance Training Exercises in Older African American Adults. - Jiakponnah, Nwanyieze; Ngozi MD, MPH; Unson, Christine; Chukwurah, Queendaleen; Chinenye MD, MPH (Gerontologist, 2021)
Background and Objectives: This study investigated the behavioral and psychological correlates of strength and balance training (SBT) participation among older African Americans. Research Design and Methods: A cross-sectional survey of 90 older African Americans (M = 66.7 ± 8.7 years; 70% female) was conducted to assess correlates of intention to undertake SBT exercises and the number of days that they currently engage in SBT. The Theory of Planned Behavior (TPB) and the threat appraisal of the Protection Motivation Theory (PMT) were used as frameworks for the analyses. Results: The intention to do SBT exercises was positively associated with favorable attitudes and subjective norm, knowledge about the benefits of SBT, and hours worked per week. The frequency of SBT participation was significantly correlated with behavioral intention, high fear of falling, and a low score on the kinesiophobia scale. Discussion and Implications: This study demonstrated the utility of the TPB and PMT's threat appraisal construct in modeling intention and number of days of SBT participation among African American older adults. The study affirmed the link between intention and behavior and between knowledge of the benefits of SBT and intention. Fear of falling's positive association with days of SBT suggests that respondents' saw SBT's efficacy in reducing falls. The unique contributions of this study are the inclusions of kinesiophobia as a correlate and multiple threat appraisals in the PMT. Health promotion interventions should consider the interrelationship among these constructs. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved.
Keywords: Accidental Falls; African American; African Americans; Aged; Attitude; Cross-Sectional Studies; Exercise; Fear; Fear of falling; Female; Humans; Intention; Kinesiophobia; Male; Psychological Theory; Subjective norm; Surveys and Questionnaires; Theory of Planned Behavior; adult; aged; article; behavior; controlled study; cross-sectional study; dept.pch; exercise; falling; fear; fear of falling; female; health promotion; human; male; motivation; peer-reviewed; prevention and control; psychological theory; questionnaire; theoretical study

The Socialization of Unpaid Family Caregivers: A Scoping Review. - McAllum, Kirstie; Simpson, Mary; Unson, Christine; Fox, Stephanie; Kilpatrick, Kelley (Res Aging, 2021)
As unpaid family caregiving of older adults becomes increasingly prevalent, it is imperative to understand how family caregivers are socialized and how they understand the caregiving role. This PRISMA-ScR-based scoping review examines the published literature between 1995-2019 on the socialization of potential and current unpaid family caregivers of older adults. Of 4,599 publications identified, 47 were included. Three perspectives of socialization were identified: (1) role acculturation; (2) role negotiation and identification; and (3) specialized role learning. The findings show how socialization involves different contexts (e.g., cultures), imperatives for action (e.g., circumstances), socialization agents (e.g., family), processes (e.g., modeling), and internal (e.g., normalization) and external (e.g., identification) consequences for caregivers. Future research could fruitfully explore how caregivers manage key turning points within the socialization process, disengage from the caregiving role, and negotiate the socialization and individualization processes within diverse cultural and funding contexts., (C)2021Sage Publications
Keywords: Aged; Caregivers; Family; Humans; Socialization; aged; care behavior; caregiver; caregiving; cultural factor; dept.pch; elder care; family; funding; human; individualization; intergenerational support; learning; negotiation; peer-reviewed; review; socialization

Application of the Weathering Framework: Intersection of Racism, Stigma, and COVID-19 as a Stressful Life Event among African Americans - Wakeel, Fathima; Njoku, Anuli (Healthcare, 2021)
The disproportionate impact of coronavirus disease 2019 (COVID-19) on African American communities necessitates an increased focus on the intersectional roles of racism, stigma, and other social determinants of health in influencing disease and mortality risk. The Weathering Framework is applied to demonstrate the dynamic interrelationships between these factors and to conceptualize COVID-19 as a stressful life event that will have profound health implications over the life course for African Americans. Recommendations for population health research, interventions and policies aimed at reducing COVID-19 incidence and mortality, and mitigation of the long-term impacts of the pandemic on communities of color are discussed.
Keywords: Blacks/African Americans; COVID-19/coronavirus; dept.pch; health disparities; peer-reviewed; race/ethnicity; racism; social determinants of health; stigma; systemic racism

Photovoice for Social Justice: Visual Representation in Action - Breny, Jean M. (Qualitative research methods ; v. 59, 2021)
"Photovoice for Social Justice, the latest volume in Sage's Qualitative Research Methods Series, helps readers in the health and social sciences learn the foundations and applications of this exciting qualitative method. Authors Jean M. Breny and Shannon L. McMorrow approach photovoice as not only a community-based participatory research method, but as a method for social justice, centering community participants, organizations, and policy makers at the heart of this research method. Special topics relating to social justice include a focus on ethics and working with marginalized communities, sensitive concerns during data collection, and presenting the work to communities and policymakers, as well as academics. Written for students and researchers new to photovoice, this brief text takes readers from the process of conceptualizing and implementing a photovoice study to analyzing data and finally presenting the results of the study. The book concludes with suggestions for future iterations of photovoice, including web based resources and digital storytelling. The authors take into account the realities of photovoice as a method by providing practical, applied tools including sample consent forms, presentations, recruitment flyers, and photo-taking tips. Using Photovoice for Social Justice, new and experienced researchers can design, implement, and analyze their photovoice projects" --
Keywords: Methodology; Medicine; Methodology; Photography in the social sciences; Participant observation; Action research; Research; Social aspects; Social service; dept.pch; faculty_collection

Police brutality against Blacks in the United States and ensuing protests: Implications for social distancing and Black health during COVID-19 - Njoku, Anuli; Ahmed, Yussuf; Bolaji, Bolanle (Journal of Human Behavior in the Social Environment, 2020)
The pandemic of respiratory disease spreading from person-to-person, named “coronavirus disease 2019” (abbreviated “COVID-19”), presents a public health emergency of international concern. This pandemic is occurring during renewed attention to the persistent issue of police brutality against Blacks in the United States. Protests have ensued to highlight perceived and observed injustice against minorities, particularly Black people. Concerns arise that these protests may complicate efforts to adhere to social distancing and increase risks of COVID-19 exposure among Black persons, who are already disproportionality affected by COVID-19 outcomes due to systemic barriers within the healthcare system and society. This article discusses police brutality against Blacks in the United States and subsequent protests, considerations for social distancing and racial disparities in health during COVID-19, and the need for policies to ensure fair and equitable enforcement of social distancing mandates. We also discuss the need for policies to improve access to COVID-19 testing, diagnosis, and management among underserved and minority communities. © 2020 Taylor & Francis Group, LLC.
Keywords: African Americans; COVID-19; Coronavirus; dept.pch; peer-reviewed; police brutality; public health

Circumstances of overdose among suburban women who use opioids: Extending an urban analysis informed by drug, set, and setting. - Lamonica, Aukje K; Boeri, Miriam; Turner, Jeffrey (The International journal on drug policy, 2021)
BACKGROUND: Opioid overdoses are primarily discussed by the pharmacological properties of the drugs used. Research shows that other factors such as the social/physical environment and the mental/emotional states can have an impact on overdose events. Ataiants and colleagues (2020) used Zinberg's "drug, set, and setting" framework to identify circumstances surrounding overdose experiences of street-involved women in Philadelphia. The aim of this paper is to extend their analysis to a diverse sample of suburban women who experienced overdoses., METHODS: The mixed-methods design consisted of ethnographic fieldwork, in-depth interviews, and brief surveys with 32 suburban women who use opioids. Inductive theoretical reasoning and constant comparative analysis facilitated themes emerging within the "drug, set, and setting" framework., RESULTS: Eighteen out of 32 women identified "drug" as the primary factor involved in their overdose events. Major themes were an inability to identify the synthetic opioid fentanyl, lack of knowledge or control over how much to use, poly-substance use, and an insufficient understanding of risks. Eleven out of 32 women linked "set" to their overdose experiences. Themes included emotional trauma, such as death of a child, child custody issues, and mental health conditions, such as depression. Six out of 32 women associated "setting" with one of their overdose experiences. Themes were related to being with friends or partners that used, and having recently been released from treatment or incarceration., CONCLUSION: Findings show similar themes found among an urban sample, adding insight on the need for effective overdose interventions targeted for suburban populations. The opioid crisis is not confined to the cities, and neither should services aimed at addressing opioid overdose. The knowledge provided here can help policy makers support female-centered harm reduction services not only in urban areas but also in the suburbs. Copyright © 2020. Published by Elsevier B.V.
Keywords: *Drug Overdose; *Pharmaceutical Preparations; Analgesics; Analgesics, Opioid/tu [Therapeutic Use]; Article; Child; Drug Overdose; Drug Overdose/dt [Drug Therapy]; Drug Overdose/ep [Epidemiology]; Female; Fentanyl; Humans; Opioid; Pennsylvania; Pharmaceutical Preparations; Philadelphia; adult; child; child custody; childhood mortality; controlled study; depression; dept.pch; drug; drug overdose; ethnography; female; fentanyl; human; incarceration; inductive reasoning; interview; major clinical study; mental health; narcotic analgesic agent; opiate addiction; peer-reviewed; polypharmacy; priority journal; psychotrauma; risk factor; suburban area; urban area; women's health

Looking back and moving forward: SOPHE's 70 years of contributions to health education. - Alber, Julia M.; Allegrante, John P.; Auld, M. Elaine; Breny, Jean M. (Health education & behavior : the official publication of the Society for Public Health Education, 2020)
Founded in 1950, the Society for Public Health Education (SOPHE) provides leadership to the health education profession and promotes the health of all people through six strategic commitments: developing and promoting standards for professional preparation and credentialing of community and school health educators; stimulating research on the theory, practice, and teaching of health education; supporting elimination of health disparities and the achievement of health equity; providing continuing education of the health education workforce; advocating for policy and legislation affecting public health and health promotion; and supporting a network of local chapters. This article describes how SOPHE has pursued these strategic commitments during the past 70 years and discusses challenges that will influence the future of SOPHE and the contours of the research and practice agendas of the field going forward. © 2020 Society for Public Health Education.
Keywords: Education, Public Health Professional; Health Education; Health Educators; Health Promotion; Humans; Public Health; SOPHE; accreditation; achievement; article; credentialing; dept.pch; education; health disparity; health education; health educator; health equity; health promotion; history; human; human experiment; law; leadership; medical education; occupation; peer-reviewed; public health; school health service; teaching; theory-practice relationship; workforce

Naloxone perspectives from people who use opioids: Findings from an ethnographic study in three states. - Boeri, Miriam W.; Lamonica, Aukje K. (Journal of the American Association of Nurse Practitioners, 2020)
BACKGROUND: Naloxone is an opioid antagonist that can reverse an opioid overdose. Increased opioid-related mortality rates led to greater distribution of naloxone without a prescription and administration of naloxone by laypersons. This study fills a gap in knowledge of naloxone experiences among active users of opioids living in suburban communities. PURPOSE: The purpose of this article is to provide nurse practitioners with an in-depth understanding of current naloxone use practices among people who experience overdose events. The specific aims are to compare access to naloxone in diverse suburban towns, to examine administration differences across settings, and to understand perspectives on naloxone experiences from people who are actively using opioids. METHODOLOGICAL ORIENTATION: The data for this analysis were drawn from an ethnographic study in the suburban towns around Atlanta, Georgia; Boston, Massachusetts; and New Haven, Connecticut. Short surveys and in-depth interviews were collected. Inductive methods were used to compare data across settings. SAMPLE: The sample of 106 included 48% female, 62% White, 24% African American/Black, 13% more than one race, and 21% Hispanic/Latinx. The mean age was 41.35 years. CONCLUSIONS: Differences between study settings in access to naloxone, administration frequency, and delivery systems were found. Findings suggest more education and training is needed in overdose prevention and harm reduction intervention. Studies on delivery systems need to address the increase in fentanyl-related overdoses. IMPLICATIONS FOR PRACTICE: Nurse practitioners can help to target distribution of naloxone in local communities, facilitate collaboration with harm reduction services, and provide evidence-based education and training to laypersons. Copyright © 2020 American Association of Nurse Practitioners.
Keywords: Adult; Analgesics, Opioid; Drug Overdose; Female; Harm Reduction; Humans; Male; Naloxone; Narcotic Antagonists; adult; dept.pch; drug overdose; female; harm reduction; human; male; naloxone; narcotic analgesic agent; narcotic antagonist; peer-reviewed

Non-motor symptoms and striatal dopamine transporter binding in early Parkinson's disease - Liu, Rui; Umbach, David M.; Troster, Alexander; Huang, Xuemei; Chen, Honglei (Parkinsonism & Related Disorders, 2020)
Background: Non-motor symptoms (NMS) are common in Parkinson's disease (PD), but their relationships to nigrostriatal degeneration remain largely unexplored. Methods: We evaluated 18 NMS scores covering 5 major domains in relation to concurrent and future dopamine transporter (DAT) imaging in 344 PD patients from the Parkinson's Progression and Markers Initiative (PPMI). We standardized NMS assessments into z-scores for side-by-side comparisons. Patients underwent sequential DaTSCAN imaging at enrollment and at months 12, 24, and 48. Specific binding ratios (SBR) were calculated using the occipital lobe reference region. We evaluated the association of striatal DAT binding at the four time points with each baseline NMS using mixed-effects regression models. Results: Multiple baseline NMS were significantly associated with DAT binding at baseline and at follow-up scans. REM sleep behavior disorder (RBD) symptoms showed the strongest association – mean striatal SBR declined with increasing RBD symptom z-score (average of time-point-specific slopes per unit change in z-score: βAVG = −0.083, SE = 0.017; p < 0.0001). In addition, striatal DAT binding was linearly associated with increasing baseline z-scores: positively for the memory (βAVG=0.055, SE = 0.022; p = 0.01) and visuospatial (βAVG=0.044, SE = 0.020; p = 0.03) cognitive domains, and negatively for total anxiety (βAVG= −0.059, SE = 0.018; p = 0.001). Striatal DAT binding showed curvilinear associations with odor identification, verbal discrimination recognition, and autonomic dysfunction z-scores (p = 0.001, p = 0.0009, and p = 0.0002, respectively). Other NMS were not associated with DAT binding. Conclusions: Multiple NMS, RBD symptoms in particular, are associated with nigrostriatal dopaminergic changes in early PD. © 2020 Elsevier Ltd
Keywords: Aged; Anxiety; Article; Autonomic Nervous System Diseases; Cognitive Dysfunction; Depression; Disruptive, Impulse Control, and Conduct Disorders; Dopamine Plasma Membrane Transport Proteins; Dopamine transporter binding; Female; Humans; Longitudinal Studies; Male; Middle Aged; Neostriatum; Non-motor symptoms; Olfaction Disorders; Parkinson Disease; Parkinson disease; Parkinson's disease; REM Sleep Behavior Disorder; Substantia Nigra; Tomography, Emission-Computed, Single-Photon; adult; aged; anxiety; autonomic dysfunction; autonomic neuropathy; clinical assessment; clinical evaluation; clinical feature; clinical trial; cognitive defect; cohort analysis; complication; controlled study; depression; dept.pch; depth perception; diagnostic imaging; disease association; dopamine transporter; evidence based practice; female; follow up; human; impulse control disorder; longitudinal study; major clinical study; male; metabolism; middle aged; motor performance; multicenter study; neostriatum; neuroimaging; occipital lobe; parasomnia; pathophysiology; peer-reviewed; priority journal; protein binding; scoring system; single photon emission computed tomography; smelling disorder; striate cortex; substantia nigra; verbal memory

Continuing the Journey Toward Health Equity: Becoming Antiracist in Health Promotion Research and Practice. - Breny, Jean (Health Education and Behavior, 2020)
Health education and promotion researchers and practitioners are committed to eliminating health disparities, and the Society for Public Health Education (SOPHE) has continuously supported this effort through its journals, professional development, annual conferences, and advocacy. The COVID-19 pandemic elucidated inequities directly caused by racism and other social determinants of health. In order to achieve health equity, we need to become antiracist in our research, practice, and advocacy work by standing united against racist policies and practices. I invite us all to heed the call to action on these five points: place racism on the agenda, practice cultural humility, claim your privilege and eliminate microaggressions, utilize strategies that promote inclusion and equity, and embrace your inner leader and activist. Just as SOPHE as an organization pivoted its annual conference from on ground to virtual in March 2020, so can we be innovative and brave as professionals to face the hard work and dedication needed to become antiracist., (C)2020Sage Publications
Keywords: Betacoronavirus; Coronavirus Infections; Coronavirus infection; Health Equity; Health Promotion; Humans; Pandemics; Pneumonia, Viral; Racism; Social Determinants of Health; antiracism; article; dept.pch; ethnology; health education; health equity; health promotion; human; human experiment; leadership; organization and management; pandemic; peer-reviewed; public health; racism; social determinants of health; virus pneumonia

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

Book Review: Lisa M.Sullivan and SandroGaleo, eds. 2019. Teaching Public Health. Baltimore, MD: Johns Hopkins University Press. $46.49. pp. 352. ISBN: 9781421429809. - Jung, Betty C. (World Medical & Health Policy, 2020)
Keywords: book review; book.review; dept.pch

Post-Graduation Impact of a Program Planning Service-Learning Project. - Risisky, Deb; Goldson, Tess; DeMezzo, Robert (Pedagog. health promot., 2020)
Research has shown that service-learning can increase student-learning outcomes across various disciplines. Service-learning opportunities have been steadily increasing in college settings, especially in health-related fields. This evaluation of an undergraduate public health course at a mid-size, public university in New England sought to understand the impact of service-learning on material retention, internships, and post-graduation public health careers. A 25-item questionnaire was emailed to students who took the course between the Fall 2010 and Spring 2016 semesters with 75 completed (33.3% completion rate). More than half of the respondents noted that their participation in a service-learning project positively affected their internship experience, their first post-graduation job, and their overall career, while also helping them retain the course material after graduation. Open-ended responses provided insight to the qualitative responses. Respondents noted that in addition to having the understanding and ability to put on programs in their community, they also had more confidence in their abilities. The opportunity to practice public speaking skills as well as work collaboratively in group settings, were both noted as essential skills needed to succeed in the public health workforce. It was concluded the project had a positive impact on student's learning and retention in planning, implementing, and evaluating an actual health promotion program as well as how they were able to use those skills in their careers., (C)2021Sage Publications
Keywords: dept.fye; dept.pch; dept.rslf; health education; peer-reviewed; program planning; service-learning

Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
Keywords: Adaptation, Psychological; Adult; African American; African Americans; Aged; Aged, 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress, Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult